GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2019)
A dataset containing 986371871 species occurrences available in GBIF matching the query: HasCoordinate: true HasGeospatialIssue: false. The dataset includes 986371871 records from 18523 constituent datasets: 19 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 7 records from Analyses of the recent components of sediment core PS1277-1. 584 records from Nannofossil abundance of Hole 60-458. 3466 records from MEXU/Leguminosae. 160 records from Waldstück Bremerhagen LK Bio Kl. 12. 1097 records from Planktic foraminifera counts of sediment core RC08-49. 32 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 235 records from Estimación de la densidad poblacional y dieta del lince (Lynx rufus) Sierra Seri, Sonora y Janos, Chihuahua. 509 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 4 records from (Table 1) PBDE and BDE congener concentration in adipose tissue of East Greenland polar bears collected 1999-2001. 62 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 561 records from Range table from benthic foraminifers in ODP Hole 146-889A. 1966 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 371 records from Bannwald Burghauser Forst. 9 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 21163 records from SEWBReC Bees, Wasps and Ants (South East Wales). 80 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 2134 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 10 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 154 records from Sorensen distance for herbivores. 89 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 111 records from Total foraminifera counts of multinet M33/1_MSN1029. 118 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260. 20518 records from University of Guam Insect Collection. 832 records from Benthic foraminifera and algae abundance of Hole 81-552A. 11565 records from National Botanic Garden Belgium - Myxomycetes. 150 records from Monocotiledóneas del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 395 records from Planktic foraminifera abundance of Hole 32-310. 26 records from Dinoflagellate abundance of Hole 81-554. 174 records from Artenvielfalt des "Grünen Klassenzimmers". 516 records from Museu de Ciències Naturals de Barcelona: BGJBB. 27670 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 495 records from Planktic foraminifera counts of sediment core A15-558. 276 records from Birds Specimens of Akita Prefectural Museum. 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 19 records from Données naturalistes de LE GLOANEC Vincent. 57451 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-64, 1974-5. 370 records from Size of planktic foraminifera at CTD station PS55/051. 41 records from MSUM Ichthyology and Herpetology Collections. 10 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 869 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 7122 records from Whale catches in the Southern Ocean. 363 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 16 records from Benthic macrofauna abundance of sediment core 13200-008. 1 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 31014 records from River Biologists' Database (EPA). 77073 records from CABI Africa Invasive and Alien Species data. 7504 records from Eurobodalla Regional Botanic Gardens. 1650 records from Great Eastern Ranges - Slopes to Summit. 75 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 79 records from Phytoplankton abundance at station Rigel_1_2005-02 in Febraury 2005, Chipana, Chile. 191294 records from Tiroler Landesmuseum Ferdinandeum. 91 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 1192 records from Pollen profile from a swamp at Seelohe, Fichtelgebirge, Germany. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 9190 records from Weddell Seal census, Vestfold Hills, Antarctica. 8851 records from Odonata records from RSPB Reserves 1970-2009. 1031 records from Données supplémentaires Atlas des Mammifères marins. 9 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 85 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 130 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 18 records from Anfibios presentes en el Cerro Jánano. 1715185 records from NBIS Records to December 2016. 149 records from Abundance of radiolaria at station UT99-23-2. 27 records from Planktic foraminifera abundance of Hole 51-417B. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 2676 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 31 records from Fundación Miguel Lillo - Colección Invertebrados. 375 records from (Appendix E) Stable carbon and oxygen isotope composition of Globigerinoides sacculifera of ODP Hole 121-758B. 2859 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 931 records from South American Antarctic Marine Biodiversity Literature. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 189 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 103 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 36 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 49 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 960 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 308 records from Naturmiljø Bergensbanen 2015 (project number 616033). 22 records from Ostracoda abundance of Hole 24-238. 21 records from Thirteen new records of ferns from Brazil. 4 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 15 records from Meiofauna abundance in sediment core 54301-010. 713 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 151 records from Collection Hydrozoa - ZSM München. 3557 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 121 records from Foraminifera abundance of sediment core IN68-28. 9057 records from NE Scotland other invertebrate records 1800-2010. 152 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 21 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 25 records from Base de données en ligne d'observations naturalistes de mammifères marins. www.faune-guyane.fr. GEPOG & LPO. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 6331 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 5 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 7 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 567 records from Foraminifera abundance of Hole 74-526A. 272 records from Dinoflagellate abundance of Hole 81-555. 48 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 797 records from Relative abundance of Neogene nannofossils at ODP Site 165-998 from the Caribbean. 1696 records from Herbier National de Guinée (HNG) (BID-AF2015-0066-REG). 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 651 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 9048 records from EDIT - ATBI in Gemer area (Slovakia). 8 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 22113 records from Global compendium of Aedes albopictus occurrence. 600 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 88 records from Teich Berlin Wuhlheide. 186 records from Nannofossil abundance of Hole 27-259. 21128 records from UTEP Vertebrates. 112 records from Creag Riabhach Wind Farm: 2012-13 Ornithology and Protected Mammal Surveys. 1110 records from (Table 2) The presence and absence of whole and/or fragmented planktonic and benthic foraminifers at DSDP Hole 93-603. 152 records from AKG-Gelände (Bensheim). 237 records from Planktic foraminifera abundance of Hole 21-207. 12 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 16 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 23 records from Benthic foraminifera abundance of Hole 93-603. 1 records from Occurrence of mammalia relicts at site Raagelund. 3 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 3983 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM. 18 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 85 records from Ostracoda abundance of Hole 48-403. 354 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 10699 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 1335 records from Walter Herwig 1978 (FFS): SeaStars (Echinodermata, Asteroidea). 15345 records from Colección Ictiológica del Instituto Alexander von Humboldt. 94 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 20 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 31 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 728 records from Planktic foraminifera counts of sediment core V27-178. 245 records from Antarctic Amphipoda. 210 records from Lebensraum Gesamtschule (Langerwehe). 425 records from Foraminifera abundance of Hole 64-481. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 2905 records from (Table A.01) Planktic foraminiferal census data of sediment core GIK23414-9. 905 records from Coléoptères Silphidés du département du Loiret. 7051 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 123 records from Total foraminifera counts of multinet M21/2_MSN648. 2356 records from Distribution of living benthic foraminifera in surface sediments of the Norwegian Sea (Table 2). 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 2380 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 177 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 16 records from Hazel Dormouse in Ireland. 106 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 30 records from Nannofossil abundance in sediment core PS1313-4. 285 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 7 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 123 records from Total foraminifera counts of multinet M21/4_MSN694. 642 records from Colección Aracnológica del IADIZA-CCT CONICET Mendoza: IADIZA-CAI. 399 records from Planktic foraminifera abundance of Hole 14-142. 39329 records from Insects, Outer Hebrides. 2 records from Distribution of Quinqueloculina sp. in sediment core 12930-014. 46 records from An der Ohm, (Wettsaasen). 51 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 149 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 7479 records from BioGIS - Vascular plants - Israeli Gene Bank. 112 records from Nannofossil abundance of Hole 73-521A. 7 records from Analyses of the recent components in the sand fraction of sediment core PS1276-1. 3 records from Range table from planktonic foraminifers in ODP Hole 169-1038E. 13527 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 10 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 91 records from Radiolaria assemblage in sediment core GIK23400-3. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 701 records from Range table from benthic foraminifers in ODP Hole 151-913B. 216 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 73 records from Rhopalocères du PNR Périgord Limousin au 15/10/2015. 1797 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 1985 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 124 records from Kirkliston Range stream monitoring. 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 3 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 10611 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 47 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 2 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 16838 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 3 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 5856 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Site 198-1213. 7887 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 5538 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 94 records from Distribution of planktonic foraminifera of sediment core SH1972_3. 88 records from Total foraminifera counts from M35/1_MSN1065. 2781 records from Marine Turtles. 196 records from Foraminifera abundance of Hole 33-317A. 670 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 120 records from Total foraminifera counts of multinet M21/2_MSN650. 6 records from Microzooplankton abundance and biomass at station NBP97-03-03-5. 6 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 210 records from Nannofossil abundance of Hole 67-499B. 3933 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 463 records from Foraminifera abundance of sediment core IN68-9. 6 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 4 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 178 records from Re-examination of the reef corals of Cocos (Keeling) Atoll, Charlie Veron. 101 records from Naturgrundstück (Eutin). 4545 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene of ODP Hole 105-645E (Table 1). 21 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 16 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 1625 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 69319 records from Données de l'Observatoire de la Faune de Bourgogne. 46 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 1168 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 1354 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 114 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 7 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 18 records from Sarcodine counts and carbon biomass at station TT012_5-PMOC5. 185 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 6466 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 350 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 837 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 73 records from (Appendix A) Sea surface temperture reconstruction for ODP Hole 117-723A. 322 records from Nannofossil abundance of Hole 49-408. 24 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 11 records from Analyses of the recent components of sediment core PS1011-1. 368 records from Biological Recording in Scotland - Bumblebee Survey. 140820 records from Allan Herbarium (CHR). 44766 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 14275 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 21 records from MVZ Herp Observations (Arctos). 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 323 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 265 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1244-2. 6 records from Foraminifera abundance of Hole 58-442. 1 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 253 records from Données naturalistes d'Olivier LAURENT. 22728 records from Restauración y conservación de Isla Guadalupe. 462 records from (Table 2) Species composition of algae and cyanobacteria encountered in plankton of the Large Aral Sea on June 2-8, 2008. 5044 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 98 records from Warnowtal (Rostock). 972 records from (Table 2) Distribution of benthic foraminifera on sediment core PS2138-1. 6 records from Wuhle - Brücke / B1. 26 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 6924 records from Marie-Victorin Herbarium (MT) - Bryophytes. 475 records from Relative abundance of dead benthic foraminifera in the large size fraction of surface sediment off NW Africa (Table 4). 318 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 2 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 5 records from (Table 2) Biomass of cysts and active infusoria in waters of the Peru coast area. 181 records from Dinoflagellate cysts from sediment core PS1295-4. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 179 records from Nannofossil abundance of Hole 24-232. 177 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 11424 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche. 1340 records from Plasm bearing foraminifera counts during METEOR cruise M36/5. 1189 records from UWIZM Molluscs. 26 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 56 records from Plasm bearing foraminifera counts of multinet M12/3_MSN562. 312 records from Nannofossil abundance of Hole 36-329. 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 149 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 104 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 115 records from Range table from planktonic foraminifers in ODP Hole 155-942C. 371 records from orthopteracollections-nhmj-ioj. 778 records from Bird specimens of Saitama Museum of Natural History. 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 6 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 413 records from (Fig. 5) Sea-surface temperature reconstructions of sediment core MD99-2304. 256 records from (Table 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-801A. 625 records from Mycology collection, Norwegian Forest and Landscape Institute. 17 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 988 records from flower availability 2008 Alb-korrigiert. 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 2808 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 22 records from Dinoflagellate abundance of Hole 14-144. 23 records from Range table from planktonic foraminifers in ODP Hole 144-874B. 6 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 35 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 34 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 3 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 237 records from Range table from benthic foraminifers in ODP Hole 161-974B. 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 173 records from UWIZM Anoles. 2845 records from Pat Livermore's Fungus Records 1976 - 2000. 7 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 444 records from Pollen analysis of sediment profile TR0 from Truennensee. 2451 records from Macrobenthos Chukchi Sea, 1986. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 208 records from Condamine Alliance. 586 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 181 records from Inventory of natural and agroforestry stands characterized by Xylopia aethiopica (Dunal) A. Rich. (south-Benin). 139 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 µm). 9 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 1168 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 367 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 15 records from Tardigrad collection of the National Museum of Nature and Science. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 4 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 1701 records from (Table 12B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-590B. 171 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 107 records from Faunal assemblage of sediment core TR149-31. 1626 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 599 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 18 records from Naturtag. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 16071 records from Herbier Louis-Marie (QFA) - Collection de lichens. 59 records from Matter enrichment of the macrofauna community of MAC station 13368-008. 164952 records from Oiseaux nicheurs de France métropolitaine 2009-2012 - Nidification probable. 93 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 204 records from Planktic foraminifera abundance of Hole 29-284A. 73 records from Planktic foraminifera abundance of Hole 49-409. 4 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 3 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 23 records from Abundance of benthos infauna at station GIK23042-2. 743668 records from Western Australian Museum provider for OZCAM. 1408 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B. 197 records from ABC_Event data recorded on a day trip to Mongolwe and Chikala Hills Forest Reserve, Machinga District. 690 records from Benthic foraminifera counts of sediment core GIK23352-3. 3983 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 419 records from Mamíferos voladores y no voladores del suroccidente colombiano. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 49 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 2782021 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 749 records from (Appendix Table 3) Relative abundances of planktonic foraminiferal species in sediment core MD01-2390. 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 164 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 33 records from Waldstück am Schullandheim Bad Bederkesa. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 1461 records from M. Gollop Collection. 334 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 1 records from Données naturalistes d'Olivier DELZONS. 218 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction. 68 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11. 164 records from Schulhof Gymnasium Hürth Bonnstrasse. 174 records from BIRDRACE Bon(n)apartemöwen. 538 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 1 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 466 records from Benthic foraminifera counts of sediment core PS1852-2. 6357 records from Distribution of foraminifera of sediment core GIK23258-2. 2606 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 1 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 5 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 326 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 38 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 235 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 412 records from Heinersdorfer Sumpfwiese. 133650 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 279489 records from ARABEL - Arachnologia Belgica. 8 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 22680 records from Arctic Species Trend Index (ASTI) : Marine. 53 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 3332 records from Dead benthic foraminifera of surface sediment of the Persian Gulf (Table 2). 33416 records from Wolli Creek Preservation Society Bird Survey. 348 records from Antarctic pycnogonids. 583 records from (Table S2) Relative abundance of coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation. 60926 records from MLZ Bird Collection (Arctos). 63 records from Inventaire des espèces végétales de la vallée de Gounti Yéna (Niamey). 126 records from Naturschutzgebiet Müchelholz (Mücheln). 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 166 records from Wiese am Waldrand (Gurtweil). 1 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 346 records from UWYMV Herpetology Collection (Arctos). 14069 records from Midden-Limburg Fish Ponds Survey. 38888 records from Herbarium Senckenbergianum (FR) - Fungi. 1994 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 6478 records from National System of Protected Areas in Poland - Animals. 170 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 240 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 5 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 158 records from Planktic foraminifera counts at CTD station PS55/063. 2829 records from (Figure 3) Stratigraphic distribution of planktonic foraminifera in the Neogene of ODP Hole 122-761B. 4193 records from Leicestershire and Rutland Aculeate Records. 177 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 2144 records from SPC CoFish Invertebrates Observations Marshall Islands 2007. 10110 records from Suivi Temporel des Libellules (STELI). 1 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 2712343 records from First Bird Atlas. 661 records from RV Investigator Voyage IN2017_V02 Seabird Observations, Australia (2017). 1 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 1 records from Reptilia ZMK. 7344 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 46339 records from University of Ghana - Ghana Herbarium. 5 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 1943 records from Pollen profile RAC20, Lake Racou, France. 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 2807 records from Natura 2000 Vallée de la Seille. 591 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 2. 10192 records from Inventario de Hymenóptera; parasítica en México. 378 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 63085 records from Alien plant presence dataset from the point-radius plot surveys in 2010-2015 in Taiwan. 3 records from Microplankton counts and carbon biomass at station TT011_8-CTD96. 8561 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 1187 records from (Table 15) Distribution of planktonic foraminifers in ODP Hole 108-666A. 67 records from Planktic foraminifera abundance of Hole 9-76. 4126 records from (Table 4) Percentages of planktonic foraminiferal taxa from the 214 surface-sediment samples from the South China Sea and the western Pacific. 715 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 76 records from BIRDRACE Nachtigallen. 68 records from Nannofossil abundance of Hole 24-233A. 1574 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 61 records from Données de Midi-Pyrénées transmises par Pascal Peyrache.. 1284 records from ConDidact Citizen Science Surveys - Amphibians 2007. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 88 records from Dinoflagellate abundance of Hole 28-274. 49 records from Total foraminifera counts of multinet FCA97C_MSN1345. 96 records from Données naturalistes (Rhopalocères et Zygènes) de Jude LOCK (indépendant). 119 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 50 records from Occurrence of mammalia relicts at site Biedermann. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 410 records from Colección Botánica-Herbario. Museo de Ciencias Naturales y Antropológicas “Juan Cornelio Moyano” (Mendoza, Argentina). 111 records from BIRDRACE Die Wendehälse. 88 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 213 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 3 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 1021 records from Phytoplankton abundance and species composition in the Gulf of Naples and the Gulf Salerno in November 1985. 186 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 8332 records from Scotland Otter Survey Database. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 1602 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 922 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 186 records from Benthic foraminifera and algae abundance of Hole 81-554. 42 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 62536 records from CAS Entomology (ENT). 24 records from Range table from benthic foraminifers in ODP Hole 178-1103A. 216664 records from Carnet B Lorraine. 27 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 480 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in East Atlantic surface sediments off Senegal and Gambia (Table 1). 451 records from Counting of benthic foraminifera of ODP Hole 182-1132B. 5 records from Nannofossil abundance of Hole 16-157A. 553 records from Radiolaria assemblage in sediment core GIK23414-6. 386 records from (Table 3) Distribution and relative abundance of planktonic foraminifers in ODP Hole 114-704A. 320 records from Myxomycetes collection of the University of Eastern Finland. 321633 records from Seasearch Marine Surveys in England. 38 records from Planktic foraminifera abundance of Hole 84-566C. 308 records from Tejidos de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 103 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 11030 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 238 records from Données Mammifères marins Aquasearch - Dauphin Passion. 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 1275 records from Biodiversidad de productores primarios de las lagunas costeras del norte de Yucatán. 2 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 1249 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 10075 records from Nematoda of Costa Rica (INBio). 83 records from Nannofossil abundance of Hole 10-89. 4 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 278 records from Nannofossil abundance of Hole 30-285A. 23648 records from WTSWW Data: All Taxa (West Wales). 614 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 213 records from Pollen record of profile 3TZ. 421246 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 192 records from "Ahrschleife bei Altenahr". 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 366247 records from South Australian Museum Australia provider for OZCAM. 2 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 35 records from Plasm bearing foraminifera counts from multinet M32/3_MSN957. 5 records from Coccolith counts of multinet M32/5_MSN981. 100 records from Brock University Herbarium (BU). 1 records from Occurrence of mammalia relicts at site Stockton-on-Tees. 220 records from (Table 1) Distribution of planktonic foraminifers in ODP Hole 126-787B. 214 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1246-4. 69 records from Unter hellen Zinnen und finsteren Grotten. 16 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 1003 records from (Table 2) Distribution of planktic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 10 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 134 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 6446 records from Modernisation des ZNIEFF du PnrL. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 129 records from Fossil occurrence of planktonic foraminifera from IODP Hole 322-C0011B. 20 records from Occurrence of mammalia relicts at site Niederlehme. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 86 records from UWIZM Cnidarians. 2 records from Microzooplankton abundance and biomass at station TT050_25-4. 80 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 148842 records from Tasmanian Museum and Art Gallery provider for OZCAM. 14095 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 938 records from TTRS Mammals. 148 records from Occurrence of mammalia relicts at site Veternica. 6 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 2 records from Benthic foraminifera abundance of Hole 42-376. 618 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 1024 records from HBRG P.F. Entwistle Notebooks Dataset. 12 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 93662 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 1 records from Occurrence of mammalia relicts at site High Furlong. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 3784 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 58 records from Occurrence of mammalia relicts at site la Grotte des Eglises. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 1140 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 227 records from Data on cetacean strandings (1999 - 2014) on the Ukrainian coast of the Black Sea and the Sea of Azov and adjoining areas. 128 records from Faunal assemblage of sediment core TR149-32. 1498 records from Nannofossil abundance of Hole 15-149. 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 1913 records from Registros Primates Neotropicales Convocatoria APC. 13 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 134 records from Pollen record of profile 3TZ2. 134 records from Planktic foraminifera counts at CTD station PS55/079-1. 36 records from Schulgelände Lise Meitner Realschule (Paderborn). 111 records from Birdrace-Uhulogen-Lippe. 8 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 12 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 7128 records from La familia Asclepiadaceae en México. 4 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 8 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 136 records from Birdrace-SpeedBirder-Zwickauer_Land. 311 records from Benthic foraminifera abundance of Hole 41-366A. 373 records from Otter survey of Ireland 2004 & 2005. 1056 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 74 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 12208 records from (Table T7) Calcareous nannofossil stratigraphy of ODP Hole 198-1210B. 111099 records from Suivi Temporel des Rhopalocères de France (STERF). 23 records from Australian Museum Ichthyology - 2012 Inscription Point. 144 records from Total foraminifera counts of multinet POS247/2_MSN1386. 411 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 23 records from Landwehrbach. 9781 records from CSIRO, fish surveys by the Soela, 1980s. 602 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 61 records from Alien Species in Poland - Plants. 1339 records from Microfossil abundance of Hole 16-158. 583 records from Nannofossil abundance of Hole 78-543. 11798 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 1156 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 35 records from Total foraminifera counts of multinet FCA97C_MSN1339. 8423 records from University Of Pretoria: Lacewing Database Project (1911-2015). 115 records from Living Cirripedia. 7 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 510 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 1031 records from ConDidact Citizen Science Surveys - Spiders 2011. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 84 records from Roter Berg Werdau (Leubnitz). 1 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 1 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 3755 records from Données naturalistes de Charlotte PICARD. 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 5 records from Ostracoda abundance of Hole 44-390. 2 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 131 records from Manejo campesino sustentable del maguey papalote del Chilapan. Fase II. 285 records from Loup 2014 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 1 records from The Shiny Cowbird, Molothrus bonariensis (Gmelin, 1789) (Aves: Icteridae), at 2,800 m asl in Quito, Ecuador. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 2 records from Neue Milbenarten aus Kärnten. 165 records from Plasm bearing foraminifera counts from M35/1_MSN1048. 163 records from Dinoflagellate cysts of ODP Hole 189-1172D. 57 records from CSIRO Yellow Box Fragmentation Project. 673 records from Planktic foraminifera abundance of Hole 45-395. 55654 records from Entomology Collection at the Natural History Museum of Utah. 23 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 79116 records from ALCB - Herbário Alexandre Leal Costa. 114 records from BIRDRACE LiLaLau. 7 records from Herbarium specimens of Limoges university (LIMO). 3750 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 49345 records from Fish specimens of Kagoshima University Museum. 26 records from (Table T8) Occurrence of Neogloboquadrina pachyderma in ODP Hole 178-1098C. 2808 records from UTEP Invertebrates (Arctos). 59 records from Schulteich Freie Waldorfschule Darmstadt. 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 10 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 684 records from Inventario de Flora de la Reserva Forestal Protectora Regional Cuchillas del Tigre, El Calón y La Osa. Municipios de San Francisco y Sonsón-Antioquia.. 163 records from Relative abundance of coccosphere-units at site GIK23414. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 12 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 4 records from Planktic foraminifera abundance of Hole 19-191A. 22052 records from CNIN/Abejas de México/Apoidea. 1331 records from (Table 2) Distribution of planktic foraminifers of sediment core D11957P. 1303 records from Flora útil del Municipio de la Huerta, Jalisco. 91 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 838 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 884 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 2067 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 159 records from Total foraminifera counts of multinet M36/6_MSN1196. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 11 records from Ostracod species in Oligocene sediments of core CRP-3. 26 records from Nannofossil abundance of Hole 10-93. 2194 records from Modelos predictivos de distribución geográfica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri. 12 records from Art´n Vielfalt im Kinderwald. 263 records from Planktic foraminifera counts of sediment core V14-77. 10 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 5472 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 302 records from UF Environmental Archaeology Tick Island Zooarchaeological Data. 251819 records from Phase 2 Lowland Grassland Survey of Wales. 385 records from Invasive Non-Native Species, Outer Hebrides. 16 records from Benthic macrofauna abundance of sediment core 13077-093. 1436 records from Naturalis Biodiversity Center (NL) - Crustacea. 60 records from Amphibian and Reptilian (KIEE-AR). 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 21 records from Brown algae specimens of Komatsu City Museum. 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 325 records from (Table 2) Abundance of ostracods in surface sediment samples from the Admiralty Bay, King George Island, West Antarctica. 78 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 480 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 1166 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 645 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE293. 1285805 records from Données issues de Clicnat (Base de données naturaliste picarde gérée par Picardie Nature). 413272 records from DATAVES. 686 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 8 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1994-D2. 9145 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 742 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 145 records from The Broward College Insect Collection. 7 records from Planktic foraminifera abundance of Hole 53-418B. 14 records from Berea College, Ralph L. Thompson Herbarium. 31 records from Macrohongos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 445 records from Distribution of nanoplankton at trap WR2. 1409 records from (Figure 6) Dinoflagellate cyst measured on sediment core AI07-12G. 13624 records from Ecosphère_2017_12_18. 11 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 151854 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 794 records from Isle of Wight non-native invasive species. 581 records from Floristic records in the Moscow and Novgorod regions. 4 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 816 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 882 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 735 records from Range table from planktonic foraminifers in ODP Hole 155-938A. 81 records from Kystfuruskoger i Tysnes og Fusa. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 29 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 91 records from Diatom abundance of Hole 95-613. 8 records from Die Bachspezies 2008/2009. 2364 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 73 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 3 records from Results of palynological analysis of Hole 302-M0004C. 45140 records from SIRFF - FNE Centre-Val de Loire - Données 2016. 68 records from Streuobstwiese. 145 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 507 records from Nannofossil abundance of Hole 66-490. 3277 records from USAC Mammals Collection. 196 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100500. 1 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 1 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 218 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 3350 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 515 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 733 records from (Table 14) Distribution of planktonic foraminifers in ODP Hole 108-665A. 50 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1018. 168 records from Occurrence of mammalia relicts at site Geißenklösterle. 270 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 2350 records from Données naturalistes de Bernard Lalanne-Cassou. 78 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 1481 records from Nannofossil abundance of Hole 82-558A. 37 records from Planktic foraminifera counts of sediment core RC13-154. 1513 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 7 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 3327 records from BioGIS - Mammals - SPNI. 21 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 29520 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 90159 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 15 records from Diatom abundance of Hole 60-460. 23 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 1200 records from Phytoplankton abundance in surface water in June 1997, Callao, Peru. 9 records from Sarcodine counts and carbon biomass at station TT011_6-CTD71. 195 records from Benthic macrofauna abundance of subcores of sediment core 13078-015. 8540 records from Collection Crustacea - ZMB. 708 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 935 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 19 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 93 records from Plasm bearing foraminifera counts from multinet SO119_MSN1284. 43 records from Nannofossil abundance of Hole 25-249. 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 372 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 4536 records from (Table 3B) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572C and 85-572D. 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 1 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 1249 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 100 records from Microzooplankton abundance measured on water bottle samples at station PS65/514-2. 143 records from Dermaptera in the icipe collection. 228 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 2344 records from (Table 2) Relative abundance of benthic foraminifera in sediment core CD17-30. 25 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 109 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 24 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 32660 records from The national database for marine data (MADS). 57 records from Nannofossil abundance of Hole 9-82. 204 records from Foraminifera abundance of Hole 57-440A. 19 records from Description of lithologic section units of IODP Hole 325-M0035A. 59 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 2332 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 6 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 102 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600. 288 records from Size of planktic foraminifera at CTD station M39/4_402CTD-55. 55 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 63-125 µm fraction. 114 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 86 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 13 records from Warnowufer Groß Klein. 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 153 records from Planktic foraminifera abundance of Hole 18-181. 220 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 16922 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 4674 records from (Table 2) Distribution of Cretaceous nannofossils at DSDP Hole 79-545. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 237 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 1004 records from Dead benthic foraminifera of surface sediments from the East Atlantic continental margin off Portugal (Table 5 & 7). 16 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-11-5. 337 records from Pollen data of trap CB4. 1481 records from Leicestershire and Rutland Mature trees Inventory 2011. 1 records from A new species of Aculus mite (Acari: Eriophyidae), a potential biocontrol agent for Australian swamp stonecrop, Crassula helmsii (Crassulaceae). 11 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0004C. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 56 records from Phytoplankton abundance at station Rigel_5_2005-02 in Febraury 2005, Chipana, Chile. 2 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 290 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-14. 136 records from Abundance of planktic foraminifera at CTD station PS55/080-1. 384 records from "Schwarzwassertal" bei Pobershau. 1932 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D. 5 records from Microfossil abundance of Hole 21-208. 217 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 928 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 1 records from Occurrence of mammalia relicts at site Ejstrup. 24493 records from Plan de vertebrados de la Patagonia. 2400 records from Springtales from lichen communities at Kollåsen in Norway. 67 records from Planktic foraminifera distribution of sediment core TRI171-27. 4515 records from Distribution of planktic foraminifera of sediment core M35003-4. 1108 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 3 records from Occurrence of mammalia relicts at site Igstadt I. 268 records from Planktic foraminifera abundance of Hole 22-217. 304444 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 132 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 975 records from Danielsberg (Mölltal, Kärnten). 8 records from Nannofossil abundance of Hole 39-353A. 16985 records from LPO_PACA_2017_12_18. 95 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 318 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 3877 records from (Table 3) Relative abundance of benthic foraminifera in sediment profile HUD84-030-04. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 740 records from Targeting a portion of central European spider diversity for permanent preservation. 10907 records from Census of species recorded during phytosociological surveys in Benin. 246 records from Nannofossil abundance of Hole 3-15. 2073 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 1558 records from (Table 3) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-707A. 64 records from (Table 4) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the upper part of the Calabianca section. 439 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 6579 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 333 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 76 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 6556 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 1 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 626 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 1 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 648 records from Range table from planktonic foraminifers in ODP Hole 155-930B. 4 records from Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae). 1014 records from Pollen profile ADR353. 97 records from Foraminifera species abundances from tow TT011_7-MOC66. 6 records from Sächsische Schweiz (Pfaffenstein). 11944 records from Données ONEMA BDMAP 2014. 564 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 1026 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 5 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 2963 records from Collection Trichoptera - SMF. 162 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 16 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 115 records from Nannofossil abundance of Hole 1-3. 130 records from Abundances of dinoflagellate cysts in sediment trap MST-9 (Appendix 1). 255 records from Occurrence of mammalia relicts at site Raj Cave. 147 records from Nannofossil abundance of Hole 6-55. 4175 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 798 records from Planktic foraminifera abundance of Hole 27-262. 96810 records from Arizona State University Hasbrouck Insect Collection. 4288 records from (Figure 5) Range chart of selected dinocysts and acritarchs of ODP Hole 104-642A. 39 records from Planktic foraminifera abundance of Hole 27-260. 2536 records from Invasive Alien Species Occurrence in Ghana. 63364 records from CCAMLR historic KRILL. 94 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 3585 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 1015 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 240 records from Chironomid remains in the sediment sequence of Site PG1212. 1480 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 3379 records from Lista florística de la Costa Grande del estado de Guerrero. 13 records from Espèces envahissantes de la Guinée forestière extraites dans la base de données de CRRA Sérédou Macenta, IRAG.. 457 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 87901 records from MDFRC macroinvertebrate survey. 62 records from Amtsrain Apolda-Zottelstedt. 76 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 245 records from (Table 9) Relative abundance of calcareous nannofossil species across the Cretaceous/Paleocene boundary at ODP Hole 120-750A. 63255 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 25 records from A revision of the genus Medmassa Simon, 1887 (Araneae: Corinnidae) in the Afrotropical Region. 53 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 58 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB03 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates. 230 records from (Table 2) Range chart for planktonic foraminifers from ODP Hole 111-677B. 120 records from Nannofossil abundance of Hole 31-299. 151 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 9476 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 390 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 55 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 99 records from Dorfrand Mauderode. 411 records from SuLaMa reptile survey I 2012. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 61 records from Shrews of Poland. 152 records from (Table 2) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-543. 9 records from Nannofossil abundance of Hole 2-11. 2 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 4 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 28711 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 269 records from Fossil occurrence of planktonic foraminifera from IODP Hole 322-C0012A. 2274 records from Planktonic foraminiferal abundances, and sea surface and export production reconstructions of sediment core SU92-03. 30 records from Nannofossil abundance of Hole 6-48B. 181715 records from Marine benthic dataset (version 1) commissioned by UKOOA. 292 records from Occurence of marine palynomorphs of sediment core CRP-1 (Table 1). 5229 records from European Moth Nights. 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 81 records from Range table from planktonic foraminifers in ODP Hole 177-1089D. 1825 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 946 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 931 records from Données naturalistes de Mathilde DUSACQ. 2068 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 3 records from MfN - Micropaleontology. 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 296 records from Table 1. Species richness and abundance of the benthic infauna of the North Sea, 1980-1985. 1036 records from BUND - Dassower See (Lübeck/Dassow). 4 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 346 records from Birds and plant species near Petushki town (Vladimir region). 1000 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 984 records from Phytoplankton abundance in surface water in September 1997, Chimbote, Peru. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 54016 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 4 records from Sächsische Schweiz (Wehlener Gebiet). 113 records from Appendicularia abundance of station M9_A near the Great Meteor Bank, Northeast Atlantic (Table 1). 1003 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 363 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 6067 records from Arthur Chapman Observations. 571 records from Cuxhavener Küstenheiden. 40 records from Planktic foraminifera abundance of Hole 14-137. 2306 records from UWYMV Bird Collection (Arctos). 1609763 records from Hatikka Observation Database. 62 records from Range table from planktonic foraminifers in ODP Hole 183-1139A. 186260 records from inatura - Erlebnis Naturschau Dornbirn. 16 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 441 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 42 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 1162253 records from PlutoF platform observations. 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 1520 records from (Table 2) Stratigraphic occurrence of selected diatom species from DSDP Hole 12-112. 2 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 136 records from Total foraminifera counts of multinet M21/6_MSN784. 5 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 8 records from Benthic macrofauna abundance of sediment core 13078-015. 84 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 41553 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 651 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 189 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB02 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 13479 records from Collection Pisces SMF. 1 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 1131 records from MEXU/Tipos de plantas vasculares. 19 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 1642 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 542 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 4 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 242 records from Landschaftspflegehof (Berlin). 10 records from Bachpatenschaft Beeke. 341 records from SPC CoFish Invertebrates Observations Niue 2005. 84 records from Total foraminifera counts from M35/1_MSN1051. 5366 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records. 91 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 390 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 167 records from Artenvielfalt auf den Elbwiesen (Dessau). 1009 records from Données naturalistes de Daniel PAVON. 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 3 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 201 records from Total foraminifera counts of multinet M21/1_MSN606. 2932 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 694 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-127. 17 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 97757 records from Denver Museum of Nature & Science - Entomology. 42 records from (Table 1) Abundance, wet biomass, and carbon biomass of all major groups of phytoplankton in the water column of the Kara Sea. 14557 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 441 records from Relative abundance of planktic foraminifera in sediment core RC08-39. 16506 records from Database for alien invasive plants occurrences in Germany. 18 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 66 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 1340 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 1151 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 533 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 84 records from Benthic foraminifera abundance of Hole 84-566C. 748 records from (Table 17) Nannoplankton distribution in sediment core ANS3-T4. 1351 records from (Appendix B) Relative abundances of larger size planktonic foraminifera in latest Maastrichtian sediments of DSDP Hole 74-525A from Walvis Ridge, South Atlantic. 2462 records from Waarneming.nl (NL) - Great Grey Shrike Count 2011-2012. 3673 records from Spider (NSMK-SP). 2390 records from OUPR - Herbário "Professor José Badini". 23 records from Nannofossil abundance of Hole 58-442B. 57217 records from National Biodiversity Data Bank. Observation records, 1900-2014. 334 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 100 records from 20th century Betula pubescens ssp. czerepanovii tree- and forest lines in Norway. 87 records from VFD-H: Heidenrod: Pferdeweide Mürth. 56 records from Total foraminifera counts of multinet M21/4_MSN720. 12413 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 104 records from Range table from benthic foraminifers in ODP Hole 172-1059B. 426 records from Données du Centre de la mer de Biarritz. 95 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 11 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 2 records from A new species of Yllenus Simon, 1868 from northern India (Araneae, Salticidae). 92 records from Nottekanal, Klasse 7 - 10. 597 records from Percentages of planktonic foraminifera species in sediment core V30-40. 595 records from Nannofossil abundance of Hole 37-333. 4845 records from Inventaire des Mollusques Sphaeriidae de France. 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 53 records from (Table 1) Fauna composition of the community of Amphiodia urtica - Nephtys ferruginea in bottom sediments from the central part of the shelf in the California upwelling zone. 3030 records from (Figure 2) Quaternary biostratigraphy and planktonic foraminifera of DSDP Hole 72-517. 78 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1389. 2004 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 1409 records from Diatom assamblage in samples from sediment trap OG5. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 3919 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 6679 records from Données issues du dispositif de Biosurveillance des Retombées Atmosphériques Métalliques par les Mousses (BRAMM). 50 records from Flora und Fauna im Brexbachtal. 898985 records from MICROBIS database. 190 records from Herpetofauna laguna El Tinije. 14619 records from Ontario Breeding Bird Atlas 1981-1985. 123 records from Birdrace-Professorenteam-Münster. 6927 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 3399 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 332 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 248680 records from Swiss National Orthoptera Databank. 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 131 records from Planktic foraminifera counts at CTD station PS55/083-1. 273 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 30091 records from BIOWIDE eDNA Fungi dataset. 45367 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 134 records from Pollen profile II/B at Krumbach, Germany. 35090 records from Computarización del Herbario ENCB. Fase I (Base de datos de los ejemplares del Valle de México). 3795 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 31 records from Nationalpark Harz Schul-AG Braunlage. 12844 records from Israeli Butterfly Monitoring Scheme (BMS-IL). 1067 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 140 records from Inventaire de la faune aviaire et de l'Ichtyofaune de la mare de l'Abarkaizé et des Oiseaux de Dan Saga. 38 records from Was lebt in der Brutzwiese?. 61 records from Phytoplankton abundance at station Sechin_2003-07-15_2, Casma, Peru. 2 records from Nannofossil abundance of Hole 4-26A. 96 records from Planktic foraminifera abundance of Hole 22-212. 28 records from Biodiversity Surveys, South-east Arnhem Land. 138472 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 45 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 383 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 39 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 6327 records from (Table 1) Dinoflagellate range chart of ODP Hole 120-748C. 86 records from Données naturalistes de Pierre-Alexis RAULT. 376028 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 151 records from Levantamento da vegetação arbustiva do Parque Nacional do Jaú. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 137 records from (Table 15) Calcareous nannofossil occurrences in ODP Hole 130-805C. 435 records from pbzt_insect_biodiversity. 3 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 253 records from NZCS Upper Tapanahony Expedition 1991. 22 records from Tanzanian Vertebrate Collection. 852 records from Phytoplankton abundance in surface water in November 1997, Pisco, Peru. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 2 records from New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae). 96 records from Coleção de Nematoda do Museu Nacional - UFRJ. 551 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 4109 records from South Caribbean Diversity. 70 records from Total foraminifera counts of multinet M21/5_MSN731. 31885 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 1803 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 1124 records from Planktic foraminifera abundance of Hole 72-516F. 4 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 1 records from Benthic foraminifera abundance of Hole 96-624. 120 records from BIRDRACE The early birds. 1289 records from RECORD Orthoptera Data. 92 records from Protozoa Abundance_Microbial Parameters. 17 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 64 records from (Table 6) Abundances of dinoflagellates in ODP Hole 104-642B. 59788 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 38 records from Antarctic Pycnogonids II. 10 records from Oberservation of birds at station PS14/143 along 49° West. 1763 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 2560 records from Upper Silesian Museum, Bird Observations. 69 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 1628 records from Données naturalistes de Quentin ROME. 798 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 223 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 126 records from SEWBReC Springtails and allies (South East Wales). 1 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 2076 records from Planktic foraminifera assemblage in sediment core SO42-74KL. 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 89 records from Nannofossil abundance of Hole 9-79. 108 records from Benthic foraminifera abundance in ODP Leg 155 holes. 158251 records from The Himalayan Uplands Plant database (HUP Version 1). 131 records from Artenvielfalt auf dem Schulgelände. 7840 records from National Museum of Natural Science. 11 records from (Table 2) Population density and zoobenthos biomass in bottom communities of the Novosibirsk Polynya in September 2008. 238 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 69 records from BIRDRACE Pfeifenten. 11 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 52 records from Collections ichtyologiques et herpétologiques (BOUM). 288 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 8516 records from Données naturalistes de Bruno OGER. 1 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 65626 records from Norwegian Lepidoptera working group. 18 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 71 records from Occurrence of mammalia relicts at site Pestera Bursucilor. 385 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 6192 records from NE Scotland fish records 1800-2010. 18 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 917519 records from SEWBReC Birds (South East Wales). 861 records from (Table 1) Percentage of Coccolithus pelagicus vs. Reticulofenestra spp. of ODP Hole 120-747A. 216 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 50940 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 569 records from (App 2) Relative contents of benthic foraminifera species in Holocene sediments from Core ASV11-858-3. 154 records from Total foraminifera counts from multinet SO119_MSN1285. 389 records from Collection Echinodermata SMF. 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 12566 records from MfN - Fossil vertebrates IV. 22 records from The fishery ground near Alexandria. XVI. Cumacea, stomatopoda, leptostraca by Adolf Steuer (1938).Notes and Memoirs No 26.. 782 records from Planktic foraminifera abundance of Hole 42-372. 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 29512 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 1607 records from MEXU/Flora de Oaxaca. 6445 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 302 records from Nannofossil abundance of Hole 66-488. 40 records from Heavy minerals of sediment core PL94-64. 5 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 131978 records from Amphibiens et Reptiles de France (Enquête 2). 3320 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 1450 records from Données naturalistes d'Alain BERLY. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 7916 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 221 records from (Table 6) Ostracod assemblages of sediment core 9409. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 368 records from Ring ouzel national sample survey in the UK in 1999. 2240 records from (Figure 7) Distribution chart of benthic foraminifers in ODP Site 126-793. 1698 records from Red-throated diver national surveys in Scotland - raw data. 215 records from (Table S2) Nannofossil abundances at DSDP Hole 86-577A. 222 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 64 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 14846 records from Données bibliographiques et opportunistes Mammifères issues du SiRF. 638313 records from Données de la flore d’Alsace (SBA). 498 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 1 records from Two new Afrotropical genera of Scatopsidae (Diptera). 5046 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 2 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 380 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 26185 records from Données de Mammifères enregistrées dans BazNat - Lot 1. 51 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/009-2. 1647 records from Nannofossil abundance of Hole 17-167. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_3-CTD39. 2 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 4 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 2744 records from Distribution of major planktic foraminifer at Site 177-1090. 122 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB02 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 1925 records from Caracterización de la vegetación en una zona delimitada en Cumbitara, La Llanada, Policarpa y Los Andes Sotomayor (Nariño), como insumo para la identificación de oportunidades de conservación para la recuperación de los servicios ecosistémicos de bosque seco. 665 records from Planktic foraminifera counts of sediment core V04-8. 132 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B. 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 110511 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 12 records from Range table from planktonic foraminifers in ODP Hole 151-912A. 4698 records from (Table 10) Eocene-Oligocene diatom biostratigraphy of ODP Hole 120-748B. 10263 records from MfN - Fossil plants (Paleophytic). 4227 records from Données naturalistes de Loïc SALAUN. 1139 records from SWECO. 1694 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 14295 records from EAC - Herbário Prisco Bezerra. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-023. 2507 records from East Ayrshire Species Database. 2565 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 5 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 11249 records from Heteroptera collections of SW Finland. 361 records from (Appendix 4, Table 4) Relative abundances of benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 9 records from Range table from planktonic foraminifers in ODP Hole 183-1136A. 692 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504. 18096 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 564 records from Atewa Range Forest Reserve Bryophytes dataset, Ghana. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 2621 records from Fungi specimens of Saitama Museum of Natural History. 1543 records from Pollen record of sediment core Bokanjacko Blato 1. 37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 7 records from Benthic hard-bottom communities abundance at X-Huinay, Comau Fjord, Chile, in 2010. 140 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 36 records from BIOMEO_2017_12_18. 211 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 841 records from Planktic foraminifera abundance of Hole 72-518. 518 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain).. 33 records from (Table 2) Distribution of early late Eocene fossil content in ODP Hole 115-714A. 78 records from (Table 10) Coiling ratio of Neogloboquadrina pachyderma of ODP Holes 127-794A and 127-197B. 3 records from A new species of Ninia (Serpentes: Dipsadidae) from Chocó-Magdalena biogeographical province, western Colombia. 630 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core PS1906-1 (Table 6). 64 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 28307 records from Bosque Mesófilo de Montaña de México. 56 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 2 records from Amphibian specimens of Obihiro Centennial City Museum. 65 records from Occurrence of mammalia relicts at site Sütto_6. 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 96508 records from Herbarium of Taiwan Forestry Research Institute. 7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 3638 records from NIWA Invertebrate Type Collection. 3 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 23 records from Ackerrain Plönhagen. 7019 records from Flora del Valle de Tehuacán-Cuicatlán: III fase. 242 records from Malawi-Histeridae-Biodiversity-Data. 1438 records from Planktic foraminifera abundance of Hole 7-64. 2149 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe’s biodiversity hotspots. 11001 records from Collections of Phytoplankton at BGBM. 3 records from Freies Projekt Speichersdorf - Region Oberfranken. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 1078 records from Pollen profile from Seminary School Basin. 25 records from Microzooplankton abundance and biomass at station TT043_4-1. 1 records from Schistura alboguttata, a new loach species of the family Nemacheilidae (Pisces: Cypriniformes) from the Pearl River basin in Guangxi, South China. 52 records from Benthic foraminifera and algae abundance of Hole 35-325. 2 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 313 records from BIRDRACE Gätkes Erben. 3036 records from (Table 13) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-715A. 3304 records from Benthos counted on dredged samples during Valdivia cruise VA53. 214 records from Total foraminifera counts of multinet M21/1_MSN608. 103 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 14110 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 5869 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 1882 records from Carabidae of the European North-East of Russia. 4011 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 1297 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 262 records from Variability of benthic Foraminifera north and south of the Denmark Strait. 6 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD63. 1143 records from Palynological analysis of sediment core GeoB9508-5. 1 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 25 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 131 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-56. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 6 records from Abundance of benthos infauna at station GIK23065-1. 27254 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 1 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 593 records from Flux data of NU2_trap (Table A1). 4 records from Planktic foraminifera abundance of Hole 17-166. 2690206 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 16 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 228 records from Bishop's University Insect Collection (BUIC). 5 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 24 records from ALTERECO_2017_12_18. 29 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 464131 records from BioFokus. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_6-CTD67. 15255 records from Anymals+plants - Citizen Science Data. 17943 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 53 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 1 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 3390 records from Planktic foraminifera abundance of Hole 23-219. 1571 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 849 records from CNAN/Scorpiones. 1 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 96 records from Total foraminifera counts of multinet M26/1_MSN845. 46 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 63-125 µm fraction. 2 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 462 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 6 records from Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey. 35 records from Nannofossil abundance in sediment core PS1293-4. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 1 records from A new species of Orthosiphon (Lamiaceae) from Angola. 424 records from Collection de C.C.H. Jongkind aux Monts Nimba (BID-AF2015-0066-REG). 458 records from Percentages of planktonic foraminifera species in sediment core V15-168. 4 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 8 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 5375 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 8 records from A review of the ant genus Metapone Forel from Madagascar.. 211 records from Nannofossil abundance of Hole 20-200. 907 records from Pollen profile Märchenwald B, Harz, Germany. 243 records from Thistles species and abundance. 61 records from Phytoplankton abundance at station Casma_2003-03-27_2, Casma, Peru. 115 records from On the absence of the Green-tailed Trainbearer Lesbia nuna (Trochilidae) from Venezuela: an analysis based on environmental niche modelling. 47 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 30-63 µm fraction. 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 1 records from Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U. S. A.. 38 records from Numbers and statistics of benthic foraminiferal Q-mode assemblages for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 2120 records from Flora vascular acuática de la cuenca del Río Tamesí. 379 records from Distribution of ostracoda in the Arctic Ocean (Table 1). 57 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Algae. 5664 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 753755 records from Inventaire National du Patrimoine Naturel : Oiseaux hivernants de France. 814 records from flower availability 2008 Hainich. 1854 records from (Table 2) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-763B, Part III. 1 records from Two new goatfishes of the genus Upeneus (Mullidae) from Australia and Indonesia. 732 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 1125 records from Données naturalistes de Stéphane ORIO. 702 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 8737 records from Andes to Amazon Biodiversity Program. 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 2 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 1551 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 774 records from Biodiversidad ictica de la Isla Cayo Serranilla Expedición Seaflower 2017 proyecto Colombia BIO. 120 records from Total foraminifera counts of multinet M21/2_MSN650. 969 records from Colecção Entomológica IIA. 6702 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 16763 records from MZFC/Coleccion de Aves. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 87 records from Nannofossil abundance of Hole 10-91. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR64. 741 records from DMNS Egg Collection (Arctos). 3402 records from (Table 2) Nannofossil occurrence in ODP Hole 101-627B. 13203 records from Lepidopterous specimens of Yamagata Prefectural Museum. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 15 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 7 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 5462 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 238 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 287870 records from Florida Keys Reef Visual Census 2014. 28 records from Phytoplankton abundance at station Casma_2003-01-30_2, Casma, Peru. 361 records from An updated checklist of aquatic plants of Myanmar and Thailand. 1702 records from BioGIS - Bryophytes - HUJ collections. 2 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 27 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 1 records from New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas. 592 records from Colección de Entomología - Curculionidae. 158 records from Planktic foraminifera counts at CTD station M39/4_402CTD-55. 13 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 440 records from Dinoflagellate cyst counts on sediment core ABC26. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 306 records from Diversity, standing stock and distribution of living benthic foraminifera suborder groups (Table 3+5). 22156 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 57452 records from Records from the NIWA AllSeaBio marine biology database. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 423 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 6230 records from Plecoptera. 5 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 9 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 80 records from Total foraminifera counts of multinet M21/4_MSN704. 146 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/088-4. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 62116 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 66 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 35 records from Nassau Mountain Expeditions 2005/2006/2010/2014. 423 records from Neogene palynomorpha from site 81-552. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 250467 records from Estonian Nature Observations Database. 38375 records from Botanical Museum, Copenhagen, Mycology Herbarium. 589 records from Birds (NMNO-BI). 1122 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 11305 records from NCSM Mammals Collection. 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 24 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 91 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 770 records from Nivå Bay species list, Zealand, Denmark. 845 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 71992 records from Colección de Entomología del Instituto Alexander von Humboldt. 7 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 164135 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2014. 2 records from Planktic foraminifera counts of multinet PS2616-5. 18 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2445-2. 4207 records from CASES2003_2004. 376 records from Digitalización y sistematización de las colecciones biológicas del INECOL. 39586 records from Fife Nature Records Centre combined dataset. 52 records from CHAS Botany Collection (Arctos). 203 records from Total foraminifera counts of multinet M21/1_MSN604. 23 records from Description of two new species of Avicularia Lamarck 1818 and redescription of Avicularia diversipes (C. L. Koch 1842) (Araneae, Theraphosidae, Aviculariinae) - three possibly threatened Brazilian species. 10 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 3 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 822 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 54 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 272 records from BIRDRACE Niederlausitz-Team. 86 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 6755 records from Odonata de Veracruz. 1464 records from Planktic foraminifera abundance of Hole 18-173. 441 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 322 records from (Table 6) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-849B. 1776 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 4421 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 1379 records from Composition of the coccolith flora in sediment core GeoB1710-3. 635 records from CG04_2017_12_18. 5 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 11 records from Collection Ephemeroptera - SMF. 33 records from Microzooplankton abundance and biomass at station TT045_15-2. 10397 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 155303 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 439 records from Collection Echinodermata - ZMB. 1 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 244 records from WildesMoor bei Schwabstedt. 435 records from Inventario herpetofaunístico del noroeste de Hidalgo. 395 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 714 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 3 records from Three new species of jumping spiders of the genus Hypaeus Simon, 1900 from Colombia (Salticidae: Salticinae: Amycini). 2 records from Description of lithologic section units of IODP Hole 325-M0052A. 9366 records from ZooplanktonBeaufortSeaNOGAP2. 7 records from Update of the genus Leptochiton (Mollusca: Polyplacophora) in Chilean deep waters: three new reports and description of two new species. 7920 records from Sinfonevada: Dataset of Floristic diversity in Sierra Nevada forest (SE Spain). 268 records from Briófitos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 190 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 13 records from Microzooplankton abundance and biomass at station NBP97-08-23-6. 150 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 1386 records from Aves de fragmentos de Bosque seco en la región del Caribe Colombiano. 4 records from Taxonomic notes on Chinese Lamiini (Coleoptera: Cerambycidae: Lamiinae). 3 records from Distribution of Quinqueloculina sp. in sediment core 13077-093. 2189 records from Jardín Botánico Atlántico, Gijón: JBAG. 26 records from Microzooplankton abundance and biomass at station TT045_26-3. 1419 records from Diversity of algae in wetlands. 1 records from Description of a new species of the Ponerine ant genus, Emeyopone (Hymenoptera: Formicidae) from Karnataka, India.. 751 records from Range table from planktonic foraminifers in ODP Hole 157-954A. 559 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 1137 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 35 records from Nannofossil abundance of Hole 15-146A. 4 records from Plasm bearing foraminifera counts of multinet POS231/3_MSN1335. 2 records from Three new species of Entomobryoidea (Collembola: Entomobryomorpha) from Brazilian Caatinga-Cerrado transition, with identification keys to Brazilian Cyphoderus, Pseudosinella and Trogolaphysa species. 1501 records from ZUEC-HEM - Coleção de Hemiptera do Museu de Zoologia da UNICAMP. 281 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Tecidos (ZUFMS-TEC). 119366 records from UWFC Ichthyology Collection. 473 records from (Table 2) Occurrence of the most abundant nannofossil taxa in middle Cretaceous sediments of ODP Leg 129 sites. 1 records from Morphological and molecular distinction of two Fridericia species (Clitellata, Enchytraeidae) having same spermatheca type. 58 records from Mamíferos laguna El Tinije. 27 records from Monophyly, review, six new species and DNA barcode of micropterous Afromontane Afropictinus (Heteroptera: Aradidae). 5546 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Queyras_2017_12_18. 17616 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 11088 records from Données naturalistes d'Anthony TURPAUD. 22 records from (Table 4a) Abundance of microalgae in surface layer bottom sediments at Station ST-RSh-1 in the northeast Black Sea. 752 records from (Table 5) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-841A. 614 records from Distribution of lithic fragments and the planktic foraminifera Neogloboquadrina pachyderma in quaternary sediments of DSDP Hole 94-609 (Table 2). 79 records from Vegetationsmatrix schorfheide alb hainich 2008 durchgang1. 80304 records from CUMV Fish Collection. 113 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200320. 6922 records from MUST, Insecta. 635509 records from Données ONF Faune-Flore-Fonge. 57 records from Distribution of planktic foraminifera of sediment core GIK23400-3. 50 records from Distribution of planktic foraminifera of sediment core PS1235-1 at stadium 5.5. 48 records from Deutsche Schule Budapest. 18 records from Occurrence of mammalia relicts at site Trebacki krs. 3 records from Amphicnemis valentini sp. nov. from the Cardamom ecoregion in Cambodia and Vietnam (Odonata: Coenagrionidae). 69399 records from University of Michigan Museum of Zoology, Division of Mollusks. 19651 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 5 records from Occurrence of mammalia relicts at site Siebenlinden 3. 122 records from M. Burton (1936). The Fishery grounds near Alexandria IX – Sponges. Notes and Memoirs No.17. Department of Zoology, British Museum. Fisheries Research Directorate. Ministry of Commerce and Industry, Egypt.. 2103 records from Flora ficológica de la huasteca potosina. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_12-CTD139. 319 records from Range table from benthic foraminifers in ODP Hole 144-874B. 293608 records from Bird tracking - GPS tracking of Western Marsh Harriers breeding near the Belgium-Netherlands border. 613 records from Données acquises via le réseau du CBNBP. 62157 records from DASSH Data Archive Centre Academic Surveys. 3769 records from Herbier de Wallis et Futuna. 1 records from First record of the thread-legged assassin bug Myiophanes greeni Distant, 1903 (Heteroptera: Reduviidae: Emesinae) from India. 3 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 322 records from Occurrence of mammalia relicts at site Roc de Combe. 148 records from Freiburger GEO-Tag der Artenvielfalt am Moosweiher in Freiburg und im angrenzenden Mooswald. 1 records from Monotypic no longer: a new species of Panca Evans (Lepidoptera: Hesperiidae: Hesperiinae: Moncini) from South America. 416 records from Data collected during the expeditions of the e-learning projects Expedition Zeeleeuw and Planet Ocean. 109 records from Exkursion Ebertsheimer/Grünstädter Berg. 269704 records from University of Florida Invertebrate Paleontology. 5 records from Endangered beauties: micro-CT cranial osteology, molecular genetics and external morphology reveal three new species of chameleons in the Calumma boettgeri complex (Squamata: Chamaeleonidae). 11 records from Données naturalistes de Thibault RAMAGE. 695 records from (Table 4) Distribution of planktonic foraminifera in middle Miocene sediments of DSDP Hole 94-608 in the North Atlantic. 736 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 43 records from Vogelstimmenführung durch den Tiergarten. 41611 records from Données naturalistes de Pierre JAY-ROBERT. 2896 records from Localizaciones satélite de un ejemplar ("Lorien") de águila azor perdicera (Aquila fasciata Vieillot, 1822) en Aragón. 96 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1362. 106 records from Evaluación de la presencia de 'Marmosa robinsoni' e inventario de mamíferos en el Departamento del Atlántico. 16738 records from Inventaire des Ephémères de métropole (Opie). 9 records from Sarcodine counts and carbon biomass at station TT012_5-TM28. 185 records from (Table 2) Range chart of benthic and planktonic foraminifera of ODP Site 127-794. 4502 records from Universidad de Barcelona (Facultad de Biología): Plantas vasculares del valle de Son del Pi y áreas colindantes. 13 records from Microzooplankton abundance and biomass at station NBP97-08-34-1. 35 records from Range table from planktonic foraminifers in ODP Hole 139-857B. 50973 records from Atlas des Orthoptères et Mantides de France métropolitaine. 315 records from (Table 1) Ostracoda community from DSDP Hole 95-612. 1418 records from Floodplain and aquatic vegetation survey, Okavango Panhandle, 2004. 20566 records from UAM Bird Collection (Arctos). 3132 records from Resolute Passage Copepod Distribution (OBIS Canada). 21 records from Twite, winter distribution in Caithness and Sutherland 2006/7. 353106 records from Dry Tortugas Reef Visual Census 2014. 26 records from Ostracoda abundance of Hole 48-406. 771 records from GEOECOLINK_2017_12_18. 217 records from Revision of the Mesoamerican species of Calolydella Townsend (Diptera: Tachinidae) and description of twenty-three new species reared from caterpillars in Area de Conservación Guanacaste, northwestern Costa Rica. 528 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 85255 records from The Scottish Squirrel Database. 96 records from BIRDRACE OAG Neuwerk. 52 records from Pittosporum sucker (Trioza vitreoradiata) records aquired by the Royal Horticultural Society. 46 records from Planktic foraminifera counts of sediment core V26-124. 42 records from (Tab. 10) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 32-303A, Japanese Magnetic Lineations east of Japan. 2 records from Two new, brachypterous Limnellia species from the Venezuelan Andes (Diptera: Ephydridae). 1 records from Acmaeodera (Ptychomus) kubani sp. n. from Northern Africa and the Arabian Peninsula, with notes on the taxonomic composition of the subgenus Ptychomus Marseul, 1866 (Coleoptera: Buprestidae: Polycestinae: Acmaeoderini). 36 records from Selz (Ingelheim am Rhein). 9594 records from Disko Fan Conservation Area in the Davis Strait (Eastern Arctic) - Epibenthic Megafauna Database. 378 records from Tsetse flies of East Africa update. 2647 records from SPC CoFish Fish Observations Nauru 2005. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 102 records from A Lichen Survey of the Ben Nevis Plateau. 387 records from Distribución espacio-temporal de las larvas de atunes en el Golfo de Tehuantepec, México. 2 records from Redescription of Zoica puellula (Simon, 1898) (Araneae: Lycosidae: Zoicinae) and transfer of Zoica harduarae (Biswas & Roy, 2008) to Agelenidae C. L. Koch, 1837. 2 records from On the taxonomy of the genus Acronicta (Lepidoptera, Noctuidae). IV. Acronicta digna species-complex. 433 records from pins. 14 records from Collection Crustacea - KAUMM. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 2146 records from Benthos, zoo- and phytoplancton data collected during the monitoring cruise of RV "Vladimir Parshin" in 1996.. 53 records from Abundance of living benthic foraminifera in sediment core CD86_09_BC1. 546 records from tree climbing bryophytes & lichens at tree base and crown with traits. 540 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/511-12. 1967 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 22853 records from Données de Lépidoptères de Denis Vandromme. 37049 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 35 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 488 records from Planktic foraminifera distribution of sediment core SU81-07. 1942 records from Collection ornithologique A. Maës. 31 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 926 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México. 1 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 4 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 46 records from Mammal specimens of Komatsu City Museum. 12 records from Urban Barcode Project - Fungi. 270 records from ACT and Southern Tablelands Weed Spotter. 41 records from Örtzemündung (Stedden). 1938 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 30233 records from National Stag Beetle Surveys (Great Stag Hunts). 609 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 2931018 records from Eremaea. 14 records from Benthic foraminifera abundance of Hole 96-620. 86616 records from Marine Offshore Seabed Survey data held by JNCC. 101 records from Nanoplankton abundance at station GeoB2006-4. 1475 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 3220 records from Natural History Museum Rotterdam (NL) - Chordata collection. 310 records from Données naturalistes de Laurent PONCET. 19 records from Coccolith counts of multinet SO119_MSN1301. 2320 records from Colección de Oligoquetos Acuáticos de la UPV/EHU. 1349 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 1275 records from (Appendix B) Dinoflagellate cysts eco-groups of DSDP Hole 38-338. 127 records from Inventario y monitoreo de aves silvestres en tres humedales del departamento de Córdoba. 9 records from Three new species of squat lobsters of the genus Fennerogalathea Baba, 1988 (Decapoda: Galatheidae) from the Pacific Ocean. 43808 records from UWBM Mammalogy Collection (Arctos). 5314 records from Dados da ocorrência de plantas lenhosas em um gradiente de perturbação/precipitação em área de Caatinga, Parque Nacional do Catimbau, Buíque, PE, Brasil. 1 records from Acromyrmex charruanus: a new inquiline social parasite species of leaf-cutting ants. 142 records from Planktic foraminifera abundance of Hole 32-313. 11110 records from Royal Ontario Museum Fungarium (TRTC). 159 records from Données de Lépidoptères de Bruno DAUGET - Dépt du CHER (18). 486 records from El código de barras de las especies NOM-059 de mamíferos del Noroeste de México. 4686 records from Butterfly_conservation_2017_12_18. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 137378 records from Cranefly (Diptera; Tipuloidea) records for Britain to 2016. 96 records from Coleoptera identified from the St. Paul's Academy site, Abbey Wood, London. 34211 records from Données bibliographiques et opportunistes Odonates issues du SiRF. 14 records from Two new species of Crocodile Skinks (Squamata: Scincidae: Tribolonotus) from the Solomon Archipelago. 138 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 3429 records from Mise en place d'un suivi scientifique des amphibiens pour la production d’indicateurs de biodiversité. 480 records from Benthic foraminifera counts of sediment core GIK23342-6. 24 records from Occurrence of mammalia relicts at site Sainte-Eulalie. 99 records from Düne am Ulvenberg (Darmstadt). 1 records from A new species of Homatula from the Red River drainage in Yunnan based on morphological and genetic data (Teleostei: Nemacheilidae). 535 records from Distribución actual y potencial de veinte especies de hongos silvestres comestibles en los bosques de coníferas del estado de Oaxaca. 17 records from Microplankton counts and carbon biomass at station TT008_5-CTD61. 659 records from Taxonomía y prospección del hábitat de las poblaciones de Bursera sect. Bullockia con especial énfasis en las especies afines al 'linaloe', B. aloexylon (Schiede ex Schlecht.) Engl.. 4294 records from Fauna and flora inventories (terrestrial and limnetic) from the South of Belgium. 172 records from Mollusca specimens of Kuroshio Biological Research Foundation. 5 records from UNM Earth Sciences Collection (Arctos). 5074 records from SPC PROCFish/C Fish Observations Papua New Guinea 2006. 10293 records from Expédition Karubenthos 2012 : inventaire des Mollusques et des Crustacés de la Guadeloupe. 2398 records from (Appendix B) Stratigraphic range and relative abundance of Neogene planktonic foraminifer taxa in ODP Hole 120-748B. 22 records from New records of ant species from Yunnan, China. 77 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 3388 records from Caracterización biológica en la Serranía de San Lucas 2015. 2394 records from EDP Baixo Sabor: Phytoplancton - Ecological Monitoring Program [2016]. 392 records from Nannofossil abundance of Hole 22-217. 1065 records from Bird specimens of Komatsu City Museum. 40 records from Marine fish and their ectoparasitic copepods in the western Wadden Sea (North Sea) in 2010. 84 records from Total foraminifera counts of multinet M21/5_MSN728. 135 records from Boreonemoral regnskog på østsiden av Lygrespollen. 26 records from Liste des oiseaux de BZM Belambo. 140 records from Beetles on polypores at 4 sites in Norway. 72 records from Range table from planktonic foraminifers in ODP Hole 180-1108B. 33 records from Collection Crustacea - ZSRO. 1590 records from Relative abundances of twenty-eight dominant benthic foraminifera species of DSDP Hole 23-219 (Table 1s). 12 records from On the spider genus Syspira Simon, 1895 (Araneae: Miturgidae) in the Caribbean: four new species from Dominican Republic. 3965 records from SPC PROCFish/C Fish Observations French Polynesia 2003, 2004 and 2006. 1547 records from Digitalización de la Biblioteca de Sonidos Naturales del Museo de Zoología, Facultad de Ciencias, UNAM. 2 records from Dysaphis (Dysaphis) kadyrovi sp. nov. — a new aphid species (Hemiptera: Aphididae) from Tajikistan. 152 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 700 records from (Appendix B) Benthic foraminiferal abundances and principal component scores in middle to late Pliocene sediments of DSDP Hole 94-610A from the North Atlantic. 157 records from BIRDRACE Rheinische Wasserrallen. 1662 records from (Table 1) Relative abundance of planktonic foraminifers in ODP Hole 164-997A sediments. 901 records from (Appendix A) Pollen and spore counts at DSDP Hole 64-480. 1 records from Revision of the genus Allometopon Kertész (Diptera: Clusiidae). 1612 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 112-681. 173 records from Plasm bearing foraminifera counts from M35/1_MSN1074. 2747 records from Données naturalistes de David HAPPE. 1 records from A second contender for “world’s smallest fly” (Diptera: Phoridae). 468 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE255. 6 records from American Asteraceae-feeding Astrotischeria species with a highly modified, three-lobed valva in the male genitalia (Lepidoptera, Tischeriidae). 1988 records from (Table 1) Planktonic foraminifera community at DSDP Hole 94-608. 107 records from Total foraminifera counts from multinet M31/2_MSN890. 3 records from Two new orthoclad species from Colombian Andes (Diptera: Chironomidae). 1057 records from Inventario y evaluación de fauna silvestre en el campo de exploración petrolera Niscota Sur. 2713 records from Relative abundances of planktonic foraminifera in ODP Site 121-758 (Table 1). 45 records from Estimated plankton abundance at station PS63/064-6. 932 records from CNAN/Araneae. 28 records from Anfibios y reptiles de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 17077 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 7 records from Checklist and taxonomic changes for Central and South American Philonthina (Coleoptera: Staphylinidae). 6 records from Anurogryllus Saussure, 1877 (Orthoptera: Gryllidae: Gryllinae) from southern Brazil: new species and new records. 79 records from Foraminifera abundance of sediment core C1960.201. 506 records from Microplankton abundance in the euphotic zone of the Aegean, Levantine and Ionian Seas in March-April 1987. 655 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS2082-1. 36280 records from EDP Foz Tua: Bat Roosts - Ecologial & Compensatory Measures Monitoring Programs [2011-2017]. 1749 records from Benthic foraminifera abundance of Hole 84-570. 1091 records from (Table 2) Benthic foraminiferal species observed in the Quaternary samples from DSDP Hole 95-613. 1359 records from GEO Biodiversity Day. 3 records from New records of lampriform fishes (Teleostei: Lampriformes) from the Pacific coast of lower Central America, with comments on the diversity, taxonomy and distribution of the Lampriformes in the eastern Pacific Ocean. 24 records from Range table from planktonic foraminifers in ODP Hole 171-1052C. 459 records from IASTracker. Invasive Alien Species database. 13204 records from Algunas especies de anfibios y reptiles contenidos en el Proyecto de Norma Oficial Mexicana PROY-NOM-059-ECOL-2000. 159 records from Planktic foraminifera assemblage in sediment core SU90-I06. 89762 records from Ornitho.eus. 105 records from Conocimiento integral del tapir (Tapirus bairdii) y el pecari de labios blancos (Tayassu pecari) en México. 187344 records from Terrestrial and liminic invertebrates systematic collection NTNU University Museum. 89 records from Total foraminifera counts of multinet POS247/2_MSN1384. 3 records from Distribution of Quinqueloculina sp. in sediment core 13200-073. 274 records from Museo Argentino de Ciencias Naturales (MACN), Buenos Aires: sea stars collection (Asteroidea, Echinodermata). 6 records from Three new species of Claudiella Reichardt & Vanin, 1976 (Coleoptera, Torridincolidae) from Brazil. 196 records from Planktic foraminifera counts of sediment core V16-20. 256 records from (App 6) Relative contents of benthic foraminifera species in sediments from Core PS2718-6. 50 records from Revision of the genus Acylophorus Nordmann, 1837 from Madagascar and Mascarene Islands (Coleoptera: Staphylinidae: Staphylininae: Acylophorina). 1 records from Laimosemion leticia (Teleostei: Cyprinodontiformes: Rivulidae), a new species from the upper Rio Amazonas, Southern Colombia. 75 records from Naturpark Kottenforst-Ville 19.6.09. 228 records from MNA (Section of Genoa) and NIWA Invertebrate Collection - Ross Sea Tanaidacea. 13 records from Review of the mirine plant bug genus Eurystylus Stål from Japan and Taiwan (Hemiptera: Heteroptera: Miridae: Mirinae), with descriptions of two new species, a new synonymy and a new combination. 73 records from Survey of slender naiad, Najas flexilis, in Loch of Butterstone and Loch of Craiglush. 62 records from Genotipificación de especies de la ictiofauna del Sistema Pánuco-Tamesí a través de la generación del código de barras de ADN mitocondrial. 795 records from UCBG TAPIR Provider. 167 records from Morfología funcional de mantos de rodolitos en el golfo de California, México. 133 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/042-2. 18 records from ZUEC-CNI - Coleção de Cnidaria do Museu de Zoologia da UNICAMP. 371 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 115-708A. 6057 records from Banco de datos de la ictiofauna del Río Bravo desde 1902 a 1992 en la colección ictiológica de la UANL. 333 records from renaturierter Main (Kemmern bei Bamberg). 353 records from Contribución a la distribución, ecología y estado de conservación de dos especies del género Sceloporus, endémicas de la región del Cabo, Baja California Sur. 155 records from (Appendix 1) Coral analysis and isostatic rebound effects from different Holes of IODP Expedition 310. 445 records from Mammals in MZNA-VERT: biology of Arvicola sapidus in Navarra. PhD project, Juan Manuel Garde. 692 records from Geochemistry and sedimentology on core POS200/10_28-1. 533 records from (App 3) Relative contents of benthic foraminifera in sediments from Core ASV1200. 226053 records from Oskarshamn herbarium (OHN). 1 records from Synthèse de la Répartition des populations de chamois en 2006 (réseau Ongulés sauvages ONCFS-FNC-FDC). 277 records from Rwanda's wetlands biodiversity data from different inventories that were conducted between year 2008 and 2017. 158 records from Michael Barkla's Observations. 72 records from Données sur les Opisthobranches et Planaires de Mayotte. 1 records from A new species of Rock Gecko of the genus Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from Belitung Island, Indonesia. 562 records from Range table from benthic foraminifers in ODP Hole 189-1169A. 38 records from (Table 1c) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the finishing of the Late Neopleistocene activity phase of the Keli Volcanic Highland. 128 records from Planktic foraminifera abundance of Hole 94-611. 168 records from (Table 1) Distribution of planktonic foraminifera species in Core ML2_66. 10 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Taynish Woods SSSI. 3 records from Abundance of zooplankton in the Aral Sea. 105 records from Fish Fauna of Berlin. 7 records from Range table from planktonic foraminifers in ODP Hole 159-959D. 5 records from Five new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China and Thailand. 1449 records from Phytoplankton abundance in surface water during cruise CD61. 29 records from Total foraminifera counts of trap L3_92_45. 2004 records from Inventaire des Coléoptères Longicornes des Antilles françaises. 6611 records from Nijmegen Natural History Museum (NL) - Herbarium. 3 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 2573320 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 105 records from Total foraminifera counts of trap L2_92_A42. 8 records from Microzooplankton abundance and biomass at station TT054_7-18. 1170 records from Département_du_Var_2017_12_18. 10 records from Occurrence of mammalia relicts at site Salzgitter-Lebenstedt. 127 records from Wildlife Observations Bardon Hill 31.5.09. 807 records from Aquatic Insects from the Caatinga: checklists and diversity assessments of Ubajara (Ceará State) and Sete Cidades (Piauí State) National Parks, Northeastern Brazil. 3 records from Tropiorhynchus annandalei (Coleoptera: Scarabaeidae: Rutelinae), a new species from Maharashtra, India. 251 records from Oxygen isotopes, Mg/Ca ratios, sea surface temperature and counting of G. ruber morphotypes of sediment core MD01-2390. 5 records from Planktic foraminifera counts of multinet M21/4_MSN724. 1491 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn). 59985 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 4203 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 4837 records from Free-living marine Nematodes from San Antonio and Cormoranes sandy beaches (Rio Negro, Argentina), 2006.. 2058 records from Table A3. Benthic foraminifera assemblage of sediment core GeoB1710-3. 1871 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv). 28 records from Two new genera and five new species of Mugadina - like small grass cicadas (Hemiptera: Cicadidae: Cicadettini) from Central and Eastern Australia: comparative morphology, songs, behaviour and distributions. 51 records from Review of the Nearctic genus Scyletria Bishop & Crosby (Araneae, Linyphiidae), with a transfer of S. jona to Mermessus O. Pickard-Cambridge. 3428 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 16 records from A new western Canadian record of Epeoloides pilosulus (Cresson), with discussion of ecological associations, distribution and conservation status in Canada. 343 records from Distribution of planktic foraminifera (250-500 µm) of sediment core GIK23059-3. 313 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_93MC. 689726 records from Finnish Floristic Database (Literature Sources). 7 records from Analyses of the recent components in the sand fraction of sediment core PS1278-1. 541 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 3336 records from (Table 14) Calcareous nannofossil occurrences in ODP Hole 130-806B. 72176 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 1773 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 197 records from Inventaire National du Patrimoine Naturel : CBN Aquitaine-Poitou-Charentes. 1 records from Microplankton counts and carbon biomass at station TT011_4-CTD46. 633 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 3 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 6550917 records from iNaturalist Research-grade Observations. 143 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C. 65 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 193 records from Nannofossil abundance of Hole 41-366A. 3 records from Two new species of the genus Cataglyphis Foerster, 1850 (Hymenoptera: Formicidae) from Iran.. 92 records from Anfibios y reptiles de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 2340 records from (Figure 10) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644B. 544 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 507 records from Planktic foraminifera abundance of Hole 84-567A. 208 records from Nannofossil abundance of Hole 39-359. 1857 records from Range table from planktonic foraminifers in ODP Hole 159-960C. 31 records from Phytoplankton abundance in surface water in 2004, Ancon, Peru. 17 records from Comunidad de Herpetos presentes en el río Tutunendo, Municipio de Quibdó-Chocó. 4159 records from DBG Mirabilis rotundifolia Demographic Monitoring. 6 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 3 records from Range table from planktonic foraminifers in ODP Hole 178-1102C. 128 records from (Appendix F) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-749C. 172 records from Nannofossil abundance of Hole 49-412. 7 records from Coeliccia rolandorum sp. nov. from eastern Cambodia and southern Vietnam, the eastern relative of C. kazukoae Asahina, 1984 (Odonata: Platycnemididae). 26 records from Abundance of benthos infauna at station PS1240-1. 611 records from Données du Râle gris sur le territoire de la Guadeloupe. 8 records from Five new species of the Acantholycosa - complex (Araneae: Lycosidae) from Mongolia. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 33 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 994 records from Amphipoda Hyperiidea of the Southern Ocean: catalogue and occurrences. 12 records from Microzooplankton abundance and biomass at station NBP97-03-12-2. 18 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5120-2. 1135 records from MarineGEO visual diver surveys of fish communities around Carrie Bow Cay, Belize, 2015. 168 records from (Table 2) Distribution of selected planktonic foraminifer species at ODP Site 124-770. 32 records from Nannofossil abundance of Hole 3-22. 2 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 477 records from Coleção de Ictiologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZIUMCN-UNIVATES). 1800 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 3063 records from Données entomologiques sur la Réserve Naturelle de l’Étang Noir. (Seignosse, Landes). Bilan des études 2001 à 2009. 5406 records from Données Lépidoptères de l'Auvergne transmises par Pascal Peyrache.. 25253 records from La colección briológica del Herbario Nacional (MEXU). Actualización 2000. 8190 records from (Table 7) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-709C. 134 records from BIRDRACE Griffin Wood Warblers. 9 records from Planktic foraminifera abundance of Hole 94-611B. 1736 records from Relative abundance of planktic foraminifera in sediment core GeoB1312-2. 1 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 2 records from Microzooplankton abundance and biomass at station TT054_24-22. 76 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003. 1452 records from Nannofossil abundance of Hole 30-286. 2476 records from Range table from benthic foraminifers in ODP Hole 154-929A. 45 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Fannich Hills SSSI. 2 records from A new pea crab species of the genus Arcotheres Manning, 1993 (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India. 53 records from Nannofossil abundance of Hole 7-63. 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 61366 records from Derek Lott Coleoptera Dataset. 2 records from Données de Lépidoptères de Bruno DAUGET - Dépt des PYRENEES-ORIENTALES (66). 2662 records from PINK - Dragonfly (Odonata) monitoring for the permanent surveillance of coastal areas in Flanders, Belgium. 41 records from Planktic foraminifera counts of sediment core V28-128. 7645 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 70 records from Incidence of pests and viral disease on pepino (Solanum muricatum Ait.) in Kanagawa Prefecture, Japan. 6541 records from Likona Invertebrates. 291 records from SuLaMa reptile survey 2013. 129368 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 257 records from Nannofossil abundance of Hole 7-62A. 3379 records from Amphibiens de Guyane. 182 records from Planktic foraminifera abundance of Hole 62-465. 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 134 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 20 records from Nannofossil abundance of Hole 3-18. 1 records from The nymph, habitat, and status of Eatonigenia in China (Ephemeroptera: Ephemeridae). 8 records from Microzooplankton abundance and biomass at station TT050_17-4. 1 records from The discovery of Euryrhynchidae (Crustacea: Decapoda) in India, with the description of a new genus and species. 225 records from L’évaluation environnementale du projet du barrage de la retenue d'eau, de Guinea Alumina corporation à sangaredi, Boké (CESP2016-022). 7 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 2898 records from DBL_Life. 4 records from New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants. 25 records from Thirteen new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China. 836 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 195 records from Pedestrian mammals census in W National Park. 1 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 29741 records from BLS Rare and Threatened Lichen Records: England. 8 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 145 records from Gronau - auf der Suche nach dem Neunauge. 141 records from Plasm bearing foraminifera counts of multinet M21/1_MSN604. 95 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 1123 records from Programme national de science participative sur la Biodiversité Littorale (BioLit). 116 records from (Table 4) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-599. 1886 records from Nannofossil abundance of Hole 94-607. 122 records from Faunal assemblage of sediment core GS7603-8. 69 records from Entdeckertour am Muldestausee 1/05. 1 records from Deux nouvelles espèces d’ Aloe L. (Xanthorrhoeaceae, Asphodelaceae), section Lomatophyllum Rowley, de Madagascar. 613 records from Implementación de la bioindicación en el Río Cauca - 2016. 1 records from Spiders of the mungaich group from Western Australia (Araneae: Salticidae: Euophryinae: Maratus), with one new species from Cape Arid. 104 records from BID-Malawi-Arctiidae-Biodiversity-Data. 2007 records from Demersal and pelagic species of fish and squid from the Patagonian shelf. 2 records from pp 56 - 66, plates 1 - 4 in Monographie des Libellulidées d'Europe. 160 records from BIOTOPE_2017_12_18. 108 records from BIRDRACE Diesmal sehen wir mehr. 1134 records from Phytoplankton abundance at several bottle stations in May 1996, Sechura, Peru. 4 records from Sangpradubina, an astonishing new mayfly genus from Thailand (Ephemeroptera: Leptophlebiidae: Atalophlebiinae). 1 records from A new species of Caligus Müller, 1785 (Copepoda: Siphonostomatoida: Caligidae) from coral reef plankton in the Mexican Caribbean. 1346 records from Weevils of Poland. 1763 records from Arachnida of Costa Rica (INBio). 188 records from Occurrence of some antimalarial plants from Cameroon. 3132 records from Ross A. Layberry, Collection. 74 records from Birdrace_Gätkes_Schergen-Helgoland. 1212 records from (Table 12) Distribution of planktonic foraminifera in the early Miocene section of ODP Hole 149-900A. 201 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/092-6. 4 records from Distribution of meiobenthos in sediment core M23_149 (2) of the northeastern Atlantic (Table 1). 143 records from Microfossil abundance of Hole 50-416A. 2 records from Tardigrada and Rotifera from moss microhabitats on a disappearing Ugandan glacier, with the description of a new species of water bear. 4 records from Microplankton abundance at bottle station SEPT-1999-K7. 11 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 4 records from Coralliidae (Anthozoa: Octocorallia) from the INDEMARES 2010 expedition to north and northwest Spain (northeast Atlantic), with delimitation of a new species using both morphological and molecular approaches. 247 records from Pollen analysis of sediment profile BLA00 from Blankensee. 7 records from Données naturalistes d'Olivier VILLEPOUX. 3 records from (Table 2) Mercury concentration in hair of Northwest Greenland polar bears (Ursus maritimus). 1822 records from Galathea II, Danish Deep Sea Expedition 1950-52. 160 records from Endofauna abundance in 2006-10 from an experiment in the Wadden Sea of List, Sylt. 274 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto29-38. 80 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM3. 86 records from Antarctic Parborlasia corrugatus. 11837 records from NCSM Non-molluscan Invertebrates Collection. 106407 records from The AAU Herbarium Database. 5 records from Description of lithologic section units of IODP Hole 325-M0046A. 7 records from Thylacosceles Meyrick new to China, with descriptions of four new species (Lepidoptera: Stathmopodidae). 69 records from (Table 3c) Distribution of planktonic foraminiferal tests in sediments from Core NKA-40T. 1 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 896 records from Sistematización de la Colección Entomológica Forestal del CENID-COMEF. 411 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 1376 records from Bird Monitoring 2017, Meise Botanic Garden. 4123 records from Colecção Entomológica do Museu de História Natural de Maputo. 209 records from Microzooplankton abundance measured on water bottle samples at station PS58/042-2. 724 records from Heritage Trees of Ireland. 44 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-10. 3 records from Three new species of Elachistidae (Lepidoptera: Gelechioidea) from India. 429 records from Distribution of agglutinated foraminifers in sediment core Well 6406/11-1. 135 records from Collection Polychaeta - ZSRO. 14061 records from imr_mareano_rpsledge. 2 records from Definition of the Lonchaea polyhamata species-group (Diptera, Lonchaeidae) with a description of new species. 224 records from Nannofossil abundance of Hole 55-433. 8 records from RISC Non-Native Species Records for Zebra Mussel. 844 records from (Table 2) Relative abundance of 13 species of planktonic foraminifers of sediment core GIK17938-2. 675 records from (Table 5) Planktonic foraminifer abundance of ODP Hole 162-982A. 93 records from Catalogue of the type specimens of Polycestinae (Coleoptera: Buprestidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 613 records from Range table from planktonic foraminifers in ODP Hole 171-1052E. 1 records from A new species of Isthmura (Caudata: Plethodontidae) from the montane cloud forest of central Veracruz, Mexico. 61 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1194. 23 records from Abundance of benthos infauna at station GIK23055-1. 50 records from Site condition monitoring of lamprey in the Endrick Water SSSI and SAC, 2012. 3 records from Three new species of Tridentella Richardson, 1905 (Isopoda: Cymothoida: Tridentellidae) from New Caledonia. 143 records from Selected Scottish freshwater fish records from 2008-2011 (collected by SEPA). 84 records from Calcareous dinoflagellate cysts of multicorer M51/3_562-5, grain fraction < 20µm. 10 records from Benthic macrofauna abundance of sediment core 13200-017. 2 records from A new species of the genus Oxyporus Fabricius (Coleoptera: Staphylinidae: Oxyporinae) in Yunnan Province, China. 528 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC08-145. 4018 records from Gunma Museum of Natural History, Fungi Specimen. 313 records from Aves de la expedición en lago de Tota, Boyacá - Proyecto Boyacá BIO. 2 records from HZI (GBF) Reichenbach Collection of Myxobacteria. 32223 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Arachnology National Collection (MACNAr). 2 records from Kirchenforst. 351 records from (Table 3) Distribution of late Cretaceous nannofossils in DSDP Hole 77-538A. 425 records from Percentages of planktonic foraminifera species in sediment core V22-38. 61 records from Range table from benthic foraminifera in ODP Hole 199-1215B. 28 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/061-3. 4 records from Two new genera and five new species of Tullbergiidae (Collembola) from the southern Appalachian Mountains of North America, with redescription of Tullbergia clavata Mills. 180 records from (Table 6) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides in DSDP Hole 79-545. 9597 records from Oiseaux nicheurs de France métropolitaine 1970-1975 - nidification possible. 2610 records from (Table 2) Pleistocene nannofossil range chart for ODP Hole 134-828A. 31 records from Salud coralina de las comunidades arrecifales de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 690 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 461 records from Distribución de peces dulceacuícolas introducidos en las cuencas del México central, con especial atención a las localidades dentro del área de distribución de los peces endémicos de la familia Goodeidae. 9446 records from Batsites inventory for England (1949-2011). 5580 records from (Table 7) Occurrence of selected diatom species in ODP Hole 119-744A. 103 records from Birdrace-Borussia_Zippammer-Bad Kreuznach. 328 records from Abundance of calcareous dinoflagellates of sediment core GeoB1214-1. 59016 records from Isopoda (Interim dataset). 759 records from Ortopteroides de Oaxaca, México: Orthoptera, Mantodea y Phasmatodea. 195 records from Plant macrofossil concentrations from an open section of Lac de Fully sediments. 250796 records from Données du CEN Picardie concernant la Faune, Flore, Fonge. 177 records from Anfibios y reptiles del municipio de Cimitarra, Santander - Proyecto Santander BIO. 253 records from Planktic foraminifera counts of sediment core RC14-7. 1 records from A New Genus and Species of Clingfish (Teleostei: Gobiesocidae) from Western Australia. 2794 records from Algae collection. 5080 records from Riqueza específica, distribución y abundancia de aves terrestres y marinas en Isla San José, Golfo de California, Baja California Sur, México. 72 records from Names of hydroids (Cnidaria, Hydrozoa) established by Charles McLean Fraser (1872 - 1946), excluding those from Allan Hancock Expeditions. 2 records from A new species of Phyllodytes Wagler, 1830 (Anura, Hylidae) from the Atlantic Forest of southern Bahia, Brazil. 5 records from Taxonomic contribution to the genus Sphaerosyllis (Annelida: Syllidae: Exogoninae) in the Black Sea. 9269 records from Relative abundance of benthic foraminifera in sediment core M5/2_KL15. 10 records from Nannofossil abundance of Hole 6-49. 4470 records from Données naturalistes de Jean-Paul LECHAPT. 55 records from Range table from planktonic foraminifers in ODP Hole 182-1130C. 2 records from Immature stages of the Australian flower-loving fly Apiocera striativentris (Diptera: Apioceridae). 3 records from Distribution of Quinqueloculina sp. in sediment core 12930-065. 68 records from Planktic foraminifera abundance of Hole 16-161. 4162 records from FNJV - Fonoteca Neotropical Jacques Vielliard. 323 records from Eco-Stratégie_2017_12_18. 1 records from Validation of Tethya samaaii Ribeiro & Muricy, 2011, replacement name for the sponge Tethya rubra Samaai & Gibbons, 2005 (Demospongiae, Tethyida, Tethyidae). 8 records from (Table 1) Mean age, body measurements, and body condition index of polar bear (Ursus maritimus) mothers and cubs. 2920 records from (Table 3) Distribution of calcareous nannofossils at ODP Hole 125-782A. 3287 records from Herpetofauna, avifauna y plantas de Puerto Salgar, Caparrapí, Guaduas y Quebradanegra (Cundinamarca). 385 records from (Table 4b) Distribution of benthic foraminifera of sediment core PS2212-3. 120 records from Succession of benthic hard-bottom communities abundance at Liliguapi, Paso Comau, Chile, in 2012. 23 records from AlgaTerraMovies. 266 records from (Table 3) Planktonic foraminifer abundance of ODP Hole 162-980A. 455 records from (Table 2f) Nannofossil distribution chart of petroleum well Montara-2. 2 records from A review of the Barsine obsoleta species-group with description of a new species from Vietnam (Lepidoptera, Erebidae, Arctiinae). 7 records from (Table 1) Biometrics and lipid content of polar bear (Ursus maritimus) adipose tissue between 1991-2007. 239 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 16998 records from Modern foraminifera in the New Zealand EEZ. 330 records from Range table from benthic foraminifers in ODP Hole 182-1126B. 15 records from Benthic macrofauna abundance of sediment core 13200-047. 9 records from Contributions to the millipede genus Nepalella Shear, 1979 from China, with four new species and first results on phylogeny based on DNA-barcoding (Diplopoda, Chordeumatida, Megalotylidae). 27 records from synthese_Protistdiversity_KG. 6279 records from SPC CoFish Fish Observations Palau 2007. 73496 records from CSIRO, North West Shelf Demersal Marine Resources Study 1980-1997. 76 records from Caracterización Floristica del Páramo Tatamá. 101 records from Planktic foraminifera abundance of Hole 28-265. 76 records from Schulgelände des Gymnasiums Nepomucenum (Coesfeld). 180 records from (Table 7) Distribution of the large, few-chambered Globigerinelloides species in DSDP Hole 79-545. 1 records from Redescription of Lernaeenicus stromatei Gnanamuthu, 1953 (Copepoda: Siphonostomatoida: Pennellidae) infesting the Black Pomfret Parastromateus niger (Bloch) from Indian waters. 101 records from Benthic foraminifera abundance of Hole 42-372. 1369 records from HUCPE - Herbário da Universidade Católica de Pernambuco. 26 records from Macroinvertebrados de la ciénaga La Honda, Tanguí. 469920 records from Natural England Marine Monitoring surveys. 756 records from Range table from benthic foraminifers in ODP Hole 139-857A. 148 records from (Table 4) Dinoflagellate cysts from sediment core PS1295-5. 3 records from A new species of the genus Protopolybia Ducke, 1905 (Hymenoptera, Vespidae, Polistinae), with taxonomic contributions to the exigua species-group. 34 records from Taxonomic revision of Agraphydrus Régimbart, 1903 I. China and Taiwan (Coleoptera: Hydrophilidae: Acidocerinae). 6 records from The Pselaphinae (Coleoptera: Staphylinidae) of Madagascar. VI. Description of Ambohitantella banari gen. et sp. n. with notes on Nearticerodes Jeannel, 1954 and Triceratomerus Jeannel, 1960. 10 records from Four new species and further contributions to the Leuctridae (Plecoptera) of the Korean Peninsula. 122 records from Foraminifera species abundances from tow TT011_10-MOC71. 546 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/544-6. 2 records from New Cheilostomata (Bryozoa) species from sublittoral and bathyal zones off the Faroe Islands, with some comments on allied taxa. 2867 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 2581 records from Phytoplankton abundance during G. M. Dannevig cruise GMD90/12. 120 records from Dead benthic foraminifera from surface sediments of the Indian and Pakistan continental margin (Table 1). 10345 records from (Appendix A) Abundances of planktonic foraminifera in mid-Pleistocene sediments of ODP Site 184-1144 in the South China Sea. 242 records from (Table 1) Bottom fauna Metazoa in grab samples from the Namibia shelf in the area of Benguela upwelling. 4387 records from Environment Agency Eiseniella tetraedra Records (England). 103 records from Range table from planktonic foraminifers in ODP Hole 170-1040B. 65 records from Total living benthic foraminifera at station M33/1_MC-25 (EAST), size fraction >30 µm. 10 records from Microzooplankton abundance and biomass at station TT050_7-9. 183 records from BID-Malawi's-Notodontidae-Biodiversity-Data. 1584 records from Coleoptera Collection. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 21647 records from National River Water Quality Network Database (Macro-invertebrates). 231 records from North Marine Region sawfish collection records (DEW collation), Australia (1912 - 2004). 371 records from Planktic foraminifera and paleoclimate temperature and salinity calculations from sediment core M44/1 GeoTü KL71. 1136 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Hymenoptera (ZUFMS-HYM). 1 records from Annotated list of Mimallonidae (Lepidoptera, Mimallonoidea) from Trinidad and Tobago, with the description of a new species of Cicinnus Blanchard, 1852 and taxonomic notes. 66 records from SNH Invertebrate Site Condition Monitoring 2013/14: Whitlaw Mosses SSSI. 13154 records from The Fungal, Lichen and Plant Collections at the Herbarium Marburgense. 264 records from DREAL_PACA_-_N2000_-_Naturalia_2017_12_18. 102 records from Waldwandel in Monschau-Mützenich-Boverei. 310 records from Manual para la identificación de lianas en el campo. 831 records from “Phytoplankton and Zooplankton data collected during the Black Sea cruises of UkrSCES R/V "Georgyi Ushakov" in 1992”. 590406 records from Welsh Invertebrate Database (WID). 14 records from Lauchhamer GEO-Tag der Artenvielfalt. 14 records from Bulletin mensuel de la société linnéenne de Lyon [1932- ]. 2171 records from (Table 2) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-763B, Part II. 4083 records from Dipterists Forum - Recording Scheme - Stilt & Stalk Flies. 36503 records from Abundances indices and biological traits of juvenile salmon sampled in the Scorff river (France). 2 records from First Australian records of Ethusina (Crustacea: Decapoda: Ethusidae) and additional records from New Zealand. 1171 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 3. 638 records from Benthic foraminifera abundance of Hole 56-435. 2 records from Microzooplankton abundance and biomass at station TT054_21-15. 16 records from Lannapsyche and Marilia species of China (Trichoptera: Odontoceridae). 14 records from Niphargus dancaui sp. nov. (Amphipoda, Niphargidae) - a new species thriving in sulfidic groundwaters in southeastern Romania. 11251 records from Données naturalistes de Pierre FRAPA. 1305 records from (Table 2) Distribution of silicoflagellates, actiniscidians, and ebridians in selected samples from ODP Hole 112-683A. 1 records from A new miniature Melanesian Forest Frog (Ceratobatrachidae: CORNufeR) from New Britain Island, constituting the first record of the subgenus BATRAchylOdes from outside of the Solomon Archipelago. 176 records from Collection Crustacea ZMG. 83 records from Naturpark Kottenforst-Ville 16.6.09. 12 records from Range table from planktonic foraminifers in ODP Hole 169-1038H. 749 records from Planktic foraminifera abundance of Hole 15-154A. 228 records from Biodiversidad acuática del río Amacuzac, Morelos, México. 661 records from Données de l'enquête Escargots de l'ONEM (onem-france.org). 1947 records from Lapwing Recovery Project, South West Scotland, 2006-2009. 146 records from Tortugas marinas de la Isla Cayos de Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 44 records from Antarctic Euphausiacea occurrence data from ITALICA 2000 Expedition. 6 records from Neotropical spittlebugs related to Neaenini (Hemiptera, Cercopidae) and the origins of subfamily Cercopinae. 118 records from Natur aus zweiter Hand am Muldestausee. 176 records from Recursos hidrobiológicos de Caño Cristales, La Macarena, Meta. 253862 records from Limnic freshwater benthic invertebrates biogeographical mapping/inventory NTNU University Museum. 190 records from Microzooplankton abundance measured on water bottle samples at station PS58/038-3. 23 records from TBW-Schafberg. 4952 records from Mamíferos de los Parques Nacionales Lagunas de Montebello y Palenque, Chiapas. 44 records from Philinidae, Laonidae and Philinorbidae (Gastropoda: Cephalaspidea: Philinoidea) from the northeastern Pacific Ocean and the Beaufort Sea (Arctic Ocean). 81 records from Cardiocondyla atalanta Forel, 1915, a cryptic sister species of Cardiocondyla nuda (Mayr, 1866) (Hymenoptera: Formicidae).. 35 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/045-2. 29 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5112-4. 9 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 30 records from Nannofossil abundance of Hole 9-82. 1964 records from Nannofossil abundance of Hole 75-530A. 24 records from Planktic foraminifera abundance of Hole 20-200A. 4 records from Collection Myriapoda - SNSD. 38 records from BB-Biodiversität a. 7248 records from DBRC Hemiptera species records 1969 to 2015. 1857 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 78612 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 1357 records from (Table 9) Benthic foraminifera in early-middle Miocene sediments of DSDP Hole 90-591B. 2163 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 151-908A. 29 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 3546 records from Dorset SW Pilot species dataset. 11 records from Benthic macrofauna abundance of sediment core 13077-087. 1914 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 420 records from (Table 2e) Nannofossil distribution chart of petroleum well Leeuwin-1. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 100 records from (Table 5) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the Lesches en Diois section. 461 records from Nannofossil abundance of Hole 24-237. 2208 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B (Table 1). 13845 records from Cumbria Non Native Invasive Species. 1 records from Description of the male of Phoebe ornator (Tippmann, 1960) (Coleoptera: Cerambycidae: Lamiinae: Hemilophini), analysis of the species biogeography, and first observation of chromatic gender dimorphism in Hemilophini. 596 records from Lower Albian l'Arboudeysse section (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 47 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 319 records from SNH Invertebrate Site Condition Monitoring 2013/14: Cairngorms SSSI. 10 records from Description of a new species of Caridina (Crustacea: Decapoda: Atyidae) from two Micronesian islands (Guam and Babeldaob). 71 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2007. 177 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 371 records from Benthic foraminifera and algae abundance of Hole 81-554A. 1056 records from Diatom assamblage in samples from sediment trap OG4. 8 records from Abundance and carbon biomass of phytoplankton at station TT007_4-CTD48. 366 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 170543 records from England Non Native Species records 1965 to 2017. 3 records from Données naturalistes d'Emilie WEBER. 41654 records from Mammals housed at MHNG, Geneva. 352 records from Phytoplankton abundance measured on water bottle samples at station PS65/424-3. 136 records from Grillhütte Wettsaasen, Wiese, Hecken. 2630 records from Swiss Psyllid (Hemiptera) Collections - Basel. 10 records from Sediment properties of core PLG95B_01BOXG. 16 records from The genus Heteragrion (Odonata: Zygoptera) in Northwestern Colombia, with the description of Heteragrion tatama sp. nov.. 2 records from New species of Trichomycterus (Siluriformes: Trichomycteridae) lacking pelvic fins from Paranapanema basin, southeastern Brazil. 537 records from Pilotovervåking av dragehode Dracocephalum ruyschiana. 130 records from Plasm bearing foraminifera counts of multinet M21/1_MSN607. 1059 records from Planktic foraminifera abundance of Hole 15-148. 260 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE206. 225 records from UWIZM Mantodea. 1 records from A new and five rare bdelloids from Korea. 1689 records from HPL - Herbário do Jardim Botânico Plantarum. 1340 records from (Figure 2) Distribution of dinoflagellate cysts in the mid-Cretaceous of ODP Hole 101-627B. 35 records from Benthic foraminifera abundance of Hole 42-381. 36 records from Total foraminifera counts of multinet M42/3_MSN1368. 753 records from Caracterización biológica de la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 2801 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1995-1999. Part 1. 123527 records from Marine data from Natural Resources Wales (NRW) Technical Support (Research & Monitoring) Contracts, Wales. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, >125 µm fraction. 2 records from Synthèse de la répartition des populations de cerf élaphe en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 9424 records from Données naturalistes (Rhopalocères et Zygènes) de Sébastien LABATUT (indépendant). 3089 records from Family Primulaceae in Virtual Herbaria of CSBG SB RAS (NSK). 13 records from A catalogue of the fishes held in the Istanbul University, Science Faculty, Hydrobiology Museum.. 2466 records from TTRS Ornithology. 313 records from Stadtpark Herzberg (Elster). 39 records from Nannofossil abundance of Hole 29-280. 131 records from Unser Schulhof - eine Apotheke. 54 records from Systematics of the family Ariidae (Ostariophysi, Siluriformes), with a redefinition of the genera.. 691 records from Black grouse national surveys. 37 records from Berlin - Treptower Park / Karpfenteich. 3 records from First record of the genus Echthronomas Forster, 1869 (Hymenoptera, Ichneumonidae, Campopleginae) for the fauna of Ukraine. 8256 records from El género Bursera en México. Parte II. 103 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 323-U1341. 17 records from Dinoflagellate cysts of sediment core IOW211630-9. 447 records from PSUZC-Mammal Collection. 161 records from (Table 2) Distribution of living benthic foraminifera in surface sediment of the Elbe estuary. 6219 records from Canadian National Collection of Insects. 245 records from Salud coralina de las comunidades arrecifales de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 7265 records from NHM, Heteroptera. 688 records from Algae, Norwegian College of Fishery Science. 34 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 105 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1372. 1067 records from Plantas de la cuenca alta y media del río Bita, Vichada (Colombia). 1 records from A new shrimp species of the genus Lebbeus White, 1847 (Crustacea: Deacpoda: Caridea: Thoridae) from a deep-sea cold seep site off southwestern Taiwan. 4 records from Review of the plant bug genus Fingulus Distant in Indochina (Hemiptera: Heteroptera: Miridae: Deraeocorini), with descriptions of two new species. 1 records from Two new Chinese species of Tomocerus at different stages of troglomorphic adaptation (Collembola, Tomoceridae). 1306027 records from Australian Museum provider for OZCAM. 1 records from 5. Wiener Gemeindebezirk. 26858111 records from Observation.org, Nature data from the Netherlands. 82 records from Phytoplankton samples - 2001/02 V3 CLIVAR. 97 records from Biological data measured on water bottle sampels at station AT_II-119/5_35-4. 13 records from Black fungus gnats (Diptera: Sciaridae) of Queensland, Australia. Part I. Genera Chaetosciara Frey, Corynoptera Winnertz, Cratyna Winnertz, Epidapus Haliday, Keilbachia Mohrig, Lobosciara Steffan, Phytosciara Frey and Scatopsciara Edwards. 4 records from On the genus Hirsutopes Pajni, 1990, (Coleoptera: Curculionidae, Entiminae), with the description of a new species. 7448 records from Mammal records for Dumfries and Galloway. 471 records from Phytoplankton data collected from a diurnal station in Sevastopol Bay (Black Sea) during 1952. 42 records from Occurrence of mammalia relicts at site Fohlenhaus-Höhlen. 34 records from Range table from planktonic foraminifers in ODP Hole 143-865A. 6 records from Occurrence of mammalia relicts at site Barova Cave. 180 records from osac_oarisma. 137164 records from Vascular plant herbarium, Tromsø Museum. 72 records from Range table from benthic foraminifers in ODP Hole 181-1121B. 183 records from Inventaire des Scléractiniaires de la région du Diahot. 36 records from Terre d'huiles. 91 records from BIRDRACE SchrägeVögel. 13716 records from NYSM Mammals. 317 records from iSpot (2008-2010): Shieldbugs & allied species. 97 records from Streuobstwiese Stedar 2008. 3 records from Lost species in Cameroon: rediscovery of the endangered freshwater crab, Louisea balssi (Bott, 1959) (Brachyura: Potamonautidae), with notes on its ecology and conservation. 205 records from Microfossil abundance of Hole 29-277. 4054 records from Dados de ocorrência de espécies da flora da Guiné-Bissau. 2017 records from Base de datos de la familia Cactaceae de la Península de Baja California, México. 91 records from Cape Darnley Early-Autumn Phytoplankton Bloom, March 2012. 232 records from Fiocruz/CEIOC - Coleção Entomológica do Instituto Oswaldo Cruz. 235 records from Absolute abundances of benthic and planktonic foraminifers in samples of ODP Hole 149-901A (Table 1). 36427 records from JPB - Herbário Lauro Pires Xavier. 57109 records from Canadian Museum of Nature Fish Collection. 17618 records from BioGIS - Mammals - INPA database. 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN743. 91 records from A revision of the spider genus Zaitunia (Araneae, Filistatidae). 6 records from On four new species of the jumping spider genus Mago O. Pickard-Cambridge, 1882 from South America (Araneae: Salticidae). 81 records from (Table 2) Absolute abundance of Contusotruncana contusa in DSDP Hole 74-527. 3729 records from (Table 3) Distribution of planktonic foraminifers in ODP Hole 112-682A. 907 records from Bats of Poland. 147 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB01 in the euphotic zone of the Aegean Sea in spring 1997. Part 3 - coccolithophores and other groups. 11 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, >150 µm. 75 records from Wiese und Bach am Kleinen Eutiner See (Eutin). 65 records from Matter enrichment of the macrofauna community of MAC station 12930-005. 63388 records from Field Museum of Natural History (Botany) Bryophyte Collection. 11 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-083BX. 95 records from Observation des mammifères sur le territoire de la Métropole Rouen Normandie. 14510 records from Coleção Ictiológica (MNRJ), Museu Nacional (MN), Universidade Federal do Rio de Janeiro(UFRJ). 2 records from What is Pseudopotamilla reniformis (Sabellidae)? Comparisons of populations from Britain, Iceland and Canada with comments on Eudistylia and Schizobranchia. 402 records from Tag der Artenvielfalt in Heidelberg. 336 records from Especies de Anacroneuria (Insecta: Plecoptera: Perlidae) de Colombia, depositadas en el Museo de Entomología de la Universidad del Valle (Cali, Colombia). 90 records from (Table 2) Occurrence of larger benthic foraminifers in ODP Hole 133-823C. 79473 records from Birds ringed by Revtangen Bird Observatory 1936-2018, Southwest Norway. 13 records from Nannofossil abundance of Hole 2-11A. 216 records from (Table A2) Stratigraphic distribution of major planktic foraminifer species of ODP Hole 198-1210A. 1703416 records from FloraCAT: Banco de datos de los cormófitos de Cataluña. 38 records from Lesser Spotted Woodpecker sample survey in England 2007. 2 records from A review of the arboreal Afrotropical ant genus Axinidris.. 30 records from Microzooplankton abundance and biomass at station TT043_21-22. 24 records from Bombus impatiens Cresson (Hymenoptera: Apidae, Apinae, Bombini) from the Prairies Ecozone in Canada. 5235 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV13. 45 records from Smear slide analysis on sediment core GeoB4223-2. 882 records from (Table T16) Planktonic foraminifera stratigraphy of ODP Hole 198-1211A, Zones P9-P12. 5576 records from Parc_Naturel_Régional_du_Queyras_2017_12_18. 9712 records from North Marine Region sea snake collection records (DEW collation), Australia (1877-2007). 72215 records from Reef Life Survey - Survey Records. 99300 records from Landesmuseum Kärnten. 15 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, 63-150 µm. 1428 records from (Table 1) Distribution of benthic foraminifers in ODP Hole 107-650A. 1398 records from Biodiversidad en las propuestas para declaratoria de Áreas Protegidas en los Municipios de Dagua, Restrepo, La Cumbre y Vijes y un Grupo de Reservas Naturales de la Sociedad Civil. 1 records from Taxonomy of the Sand Sliders of Western Australia’s central coast (genus Lerista, Squamata: Scincidae): recognition of Lerista miopus (Günther, 1867). 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 198 records from Planktic foraminifera distribution of sediment core 75KS5. 32 records from Nannofossil abundance of Hole 26-250. 1 records from New species and records of the Pericoma trifasciata group from Croatia (Diptera: Psychodidae). 16 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-17-4. 2382 records from Bay of Fundy Species List. 445 records from Pollen analysis of sediment profile BLA0 from Blankensee. 1 records from Revision of the genus Celebargiolestes Kennedy, 1925 (Odonata: Argiolestidae). 10 records from Notes on the Rhyacophila angulata Species Group with descriptions of two new species (Insecta, Trichoptera, Rhyacophilidae). 3 records from Ostracoda abundance of Hole 13-134. 313 records from VIP topsoil data jointsampling soilfauna, 2008. 20 records from Revision of the genera Pareuthria Strebel, 1905, Glypteuthria Strebel, 1905 and Meteuthria Thiele, 1912 (Gastropoda: Buccinulidae) with the description of three new genera and two new species from Southwestern Atlantic waters. 81 records from Planktic foraminifera abundance of Hole 14-136. 622 records from Composition of the coccolith flora in sediment core K708-007. 21482 records from UPCB - Herbário do Departamento de Botânica. 385 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE278. 10 records from A new species of Probolomyrmex from Madagascar.. 952 records from Guinea-Bissau Herpetological Collection - IICT. 78 records from (Table 3) Downcore distribution of live benthic foraminifera of sediment core SW_2b, California continental borderland. 24 records from Dinoflagellate cysts of sediment core IOW211670-7. 908 records from Códigos de barras del ADN de mamíferos topotipos de México Fase I: Noroeste mexicano. 5 records from Planktic foraminifera abundance of Hole 19-184B. 10786 records from Camera trapping bird data. 85 records from Planktic foraminifera counts of sediment core V27-47. 517 records from Crustáceos macrobénticos de la plataforma y talud continental del Golfo de México. 2 records from Notes on the genus Yunnantettix Zheng (Tetrigidae: Cladonotinae), with descriptions of two new species from Thailand. 1490 records from Database of Eurasian beaver (Castor fiber L., 1758) in Natural Reserves and National Parks of Russia. 291 records from Phytoplankton abundance at bottle station A1/52. 1023 records from Poliquetos invasores (Annelida: Polychaeta) del Puerto de Mazatlán, Sinaloa. 6438 records from ZFMK Coleoptera collection. 322 records from Nannofossil abundance of Hole 67-497. 261 records from Range table from planktonic foraminifers in ODP Hole 170-1043A. 144 records from Lustbach-Umland. 125 records from annex3. 35171 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 43160 records from Ireland's BioBlitz. 23 records from Benthic macrofauna abundance of sediment core 13200-075. 2258 records from Muscidae (Diptera) records from Britain and Ireland to 1985. 336 records from Eschlberg Thalhausen. 58 records from Review of selected species of Campsurus Eaton 1868 (Ephemeroptera: Polymitarcyidae), with description of eleven new species and a key to male imagos of the genus. 234 records from Loup 2012 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 1 records from Integration of molecular, bioacoustical and morphological data reveals two new cryptic species of Pelodytes (Anura, Pelodytidae) from the Iberian Peninsula. 34 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB01 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 188 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_91MC. 506 records from (Table T1) Planktonic and benthic foraminifer abundance of ODP Hole 183-1138A. 46 records from Revision of the genus Odocnemis Allard, 1876 (Coleoptera: Tenebrionidae: Helopini) from Turkey, the Caucasus and Iran with observations on feeding habits. 2303 records from Benthic foraminifers of sediment core Svanic90_9004. 70 records from Range table from planktonic foraminifers in ODP Hole 173-1067A. 2 records from A new species of Angaeus from Malaysia with possible affinity to related genera within Stephanopinae (Araneae: Thomisidae). 74 records from Abundance of Lanice in 2007-03 from an experiment in the Wadden Sea off List, Sylt. 17 records from Review of the genus Eburodacrys White, 1853 (Coleoptera: Cerambycidae: Cerambycinae). 149 records from Trockenhang Greinhartsberg Edelfingen. 67367 records from European Invertebrate Survey (EIS-NL) - Orthoptera Observations. 18 records from Locations at sea of adult females of southern elephant seals (Mirounga leonina) from Península Valdés, Chubut, Argentina. 62 records from Tag der Artenvielfalt BUND Kaiserslautern. 1098 records from Caracterización biológica de la ventana de biodiversidad del Complejo Cenagoso de Zapatosa, Municipio de Chimichagua, Cesar, Colombia. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1995-D2. 1136 records from National Taiwan Museum. 537 records from Données naturalistes de Christophe HERVE. 56 records from (Table 3) Quantitative parameters of the Emiliania huxleyi population along the section from the Pribilofs Islands to the Nunivak Island carried out on 24 and 25 August 2001. 456 records from Levantamento de Arbóreas do Parque Nacional do Jaú. 1351 records from (Table T9) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones P5-P7. 19 records from Inventaire National du Patrimoine Naturel : Données sur Tamias sibiricus (Ecureuil de Corée). 471508 records from SER Species-based Surveys. 191 records from Fauna inventories from the intertidal zone in Wimereux, France. 211401 records from River Macrophytes Database. 3 records from A new species of the alpheid shrimp genus Thuylamea Nguyên, 2001 (Crustacea: Decapoda: Caridea) from Yatsushiro Sea, Kyushu, Japan. 800 records from (Table 1) Distribution of larger benthic and planktonic foraminifers in ODP Hole 135-841B. 158456 records from NINA insect database. 5 records from Cirrhigaleus australis n. sp., a new Mandarin dogfish (Squaliformes: Squalidae) from the south-west Pacific.. 5 records from The Neotropical species of Clistopyga (Hymenoptera, Ichneumonidae, Pimplinae). Part II: the C. isayae species group, with the description of seven new species. 240 records from Foraminiferal paleotemperatures (MAT) and relative abundances from core M23414 (GIK23414-9). 274 records from Macromycetes in Portugal Update. 3 records from A new spider species of the genus Sudharmia from Sumatra, Indonesia (Araneae, Liocranidae). 40 records from (Supplementary Table 2) Estimates of bottom-water oxygenation at site GeoB11185-1. 3000 records from Fortalecimiento de la Colección de fotocolectas biológicas (CFB): una propuesta del uso de la imagen digital al servicio del conocimiento de la biodiversidad. 100 records from orstom_macassar_corindon_1980. 5295 records from PNR_Alpilles_2017_12_18. 36310 records from Lichen herbarium TRH, NTNU University Museum. 5133 records from (Figure 3) Distribution chart of creatceous planktonic foraminifera of ODP Hole 122-762C. 69 records from Planktic foraminifera abundance of Hole 32-313. 93 records from Höltigbaum. 2 records from First record of ectoparasitic ciliates, of genus Trichodina (Ciliophora: Trichodinidae) parasiting cultured Oranda Gold Fish (Carassius auratus auratus L.) in India. 41 records from A taxonomic revision of the catshark genus Holohalaelurus Fowler 1934 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae), with descriptions of two new species.. 31 records from A new East African genus of spirostreptid millipedes (Diplopoda, Spirostreptida, Spirostreptidae), with notes on their fungal ectoparasite Rickia gigas. 7600 records from (Figure 6) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-550. 245 records from Distribution of planktic foraminifera (250-500 µm) of sediment core GIK17732-1. 1 records from Synthèse de la Répartition des populations de daim en 2013 (réseau Ongulés sauvages ONCFS-FNC-FDC). 2034 records from Actualización de la base de datos de helmintos parásitos de peces de agua dulce de México. 99 records from BIRDRACE TEAM BO-BACHTER. 56 records from Zitadelle Berlin-Spandau (7b). 1 records from Crenicichla ploegi, a new species of pike-cichlid of the C. saxatilis group from the Rio Juruena and upper Rio Paraguai basins in Brazil, with an updated diagnosis and biogeographical comments on the group (Teleostei: Cichlidae). 3224 records from Distribución geográfica de las lagartijas partenogenéticas del género Aspidoscelis en México. 4365 records from General Biodiversity Records from Ireland. 268 records from Inventaire forestier en forêt tropicale primaire de Guadeloupe. 429 records from Di
Keywords: GBIF; biodiversity; species occurrences